Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 328095556 species occurrences available in GBIF matching the query: { "or" : [ "Month is January", "Month is December", "Month is February" ] } The dataset includes 328095556 records from 15625 constituent datasets: 2 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 17 records from Sea Turtles of Dominica (aggregated per 1-degree cell). 554 records from Suivi des aires marines protégées de Moorea - Invertébrés benthiques. 3 records from MVZ Herp Observations (Arctos). 3 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 98 records from CRC HRC Shore-based Surveys KB11 2013-2015. 5207 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 10 records from Analyses of the recent components of sediment core PS1277-1. 1 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 2591 records from MEXU/Leguminosae. 6 records from Foraminifera abundance of Hole 58-442. 139 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 26 records from MIRC NAVFAC Incidental Sightings - Aerial 1965-2014. 899 records from Planktic foraminifera counts of sediment core RC08-49. 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 65 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 2 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 6085 records from Restauración y conservación de Isla Guadalupe. 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 312 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 1 records from A review of the Glossogobius giuris complex in Australia, with wider discussion on nomenclature and possible synonymies. 6 records from Coleção de Coleoptera da Universidade de Brasília. 1648 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 1007 records from Microbial ecology of archaeal community in sediment from adjacent waters of Rushan Bay. 1806 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 352 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 6 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 1 records from New England Aquarium Harbor Porpoise Tracking (aggregated per 1-degree cell). 18 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 1 records from A review of the subfamily Anobinae with the description of a new species of Baniana Walker from North and Central America (Lepidoptera, Erebidae, Anobinae). 15 records from The genus Litophyton Forskål, 1775 (Octocorallia: Alcyonacea: Nephtheidae) from Australia. 5 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 569 records from SEWBReC Bees, Wasps and Ants (South East Wales). 661 records from Fitoplancton de la provincia oceánica del mar Caribe colombiano. Diez años de historia. 591 records from Marie-Victorin Herbarium (MT) - Bryophytes. 8 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 74 records from UCSC Elephant Seals (aggregated per 1-degree cell). 417 records from Relative abundance of dead benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 4). 2 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 7 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 90 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 22 records from Bostryx tortoranus (Doering, 1879) species complex (Gastropoda: Stylommatophora: Bulimulidae), a review of taxonomy and distribution of endemic species from Argentina. 7110 records from National Benthic Inventory. 1 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 971 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 349 records from COA Bird Collection (Arctos). 34 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 1327 records from Bryophyte specimens of The Nagoya University Museum. 6457 records from University of Guam Insect Collection. 183 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 517 records from Scotland Otter Survey Database. 56 records from Museu de Ciències Naturals de Barcelona: BGJBB. 120 records from Intermountain Herbarium (fungi, not lichens), Utah State University. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 2 records from The identity of Osteobrama cotio, and the status of “ Osteobrama serrata ” (Teleostei: Cyprinidae: Cyprininae). 2 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 1139 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 129 records from AMAPPS Southeast Aerial Cruise Fall 2016. 227 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 2140 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche (Plantas). 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 1 records from Revision of Afrotropical species of the Philonthus peripateticus species group (Coleoptera: Staphylinidae: Philonthina). 1 records from Dressed in black. A New Ansonia Stoliczka, 1870 (Lissamphibia: Anura: Bufonidae) from Gunung Murud, Sarawak, East Malaysia (Borneo). 164 records from UWIZM Molluscs. 1935 records from MCP-Aves - Coleção de Aves. 19067 records from CAS Entomology (ENT). 7845 records from Carnet B Lorraine. 18868 records from Naturalis Biodiversity Center (NL) - Pisces. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 1 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 448 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 1). 313 records from Bird specimens of Saitama Museum of Natural History. 5 records from Nannofossil abundance of Hole 16-157A. 4 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 6 records from Myxomycetes collection of the University of Eastern Finland. 52 records from Collections of Bioclass, school #179, Moscow. 672 records from BLM CETAP AIR Sightings. 4 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 8 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 11206 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 6356 records from Seasearch Marine Surveys in England. 27 records from Planktic foraminifera abundance of Hole 84-566C. 12 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 11 records from Mycology collection, Norwegian Forest and Landscape Institute. 21 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 30 records from Abundances of dinoflagellate cysts in sediment trap MST-9 (Appendix 1). 155 records from Condamine Alliance. 1910 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 5130 records from Arizona State University Hasbrouck Insect Collection. 53 records from Invasive Alien Species Occurrence in Ghana. 15 records from Collection Strepsiptera SMF. 8 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 428 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 519 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 1 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 5 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 14 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 2 records from Tardigrad collection of the National Museum of Nature and Science. 552 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 1107 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 3430 records from Microbial community in marine sediments. 422 records from Lista florística de la Costa Grande del estado de Guerrero. 1 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 13 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 141 records from Herbier Louis-Marie (QFA) - Collection de lichens. 76 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 3 records from Happywhale - Adelie Penguin in Southern Ocean. 25970 records from MDFRC macroinvertebrate survey. 45 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 4 records from A New Genus And Species Of Orsillinae (Heteroptera: Lygaeoidea: Lygaeidae) From Argentina. 2779 records from Plant. 2 records from Two new pill millipedes (Diplopoda: Glomerida: Glomeridae) from high mountains of Vietnam. 11192 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 25 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 14 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 2 records from A New Species Of Isoperla Banks (Plecoptera: Perlodidae) From The Southern Appalachians, With Notes On The I. Montana Group. 7448 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 3 records from Contributions to the knowledge of Dichelops (Dichelops) with the description of a new species (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 2 records from Four new Oriental species of the ‘ Cephennomicrus group’ (Coleoptera: Staphylinidae: Scydmaeninae). 2 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 2967 records from Colecção Entomológica IIA. 16 records from Catalogue of the Syrphidae of Egypt (Diptera). 30070 records from 16S sequencing of environmental samples to test the impact of sediment source. 4171 records from MZFC/Coleccion de Aves. 640 records from Coleópteros presentes en un proceso de restauración pasiva en bosque seco tropical. 7 records from Dubai Turtle Rehabilitation Project (aggregated per 1-degree cell). 72 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 20 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 122 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 1 records from Shrews of Poland. 708 records from DMNS Egg Collection (Arctos). 1 records from Happywhale - Layard's beaked whale in Southern Ocean. 9 records from K-State Museum of Entomological and Prairie Arthropod Research. 267 records from A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae - Grewioideae). 378 records from (Table 2) Nannofossil occurrence in ODP Hole 101-627B. 159 records from Lepidopterous specimens of Yamagata Prefectural Museum. 2 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 156 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 4190 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 1 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 19 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 10540 records from Marine benthic dataset (version 1) commissioned by UKOOA. 65 records from Happywhale - Humpback Whale in Arctic Ocean. 17 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 11 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 1 records from The diversity of the genus Aricidea (Polychaeta: Paraonidae) from the Sea of Marmara, with descriptions of two new species and two new records for the Mediterranean fauna. 1239 records from The Dolphin Project. 28 records from Orthoptera - SMF. 926 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 3 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 65 records from Range table from planktonic foraminifers in ODP Hole 177-1089D. 1137 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 2070 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 289 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 1 records from A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes: Heptapteridae) from the Orinoco River basin. 22 records from Visual and genetic surveys for odontocete cetaceans in American Samoa 2003-06. 12 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 24624 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 118 records from An updated checklist of aquatic plants of Myanmar and Thailand. 28 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru. 1 records from Registro de Chromolaena tacotana asociado al proyecto: Relación estructura-actividad anti-cáncer de flavonoides sobre líneas celulares cancerosas. 556 records from BioGIS - Bryophytes - HUJ collections. 89 records from Etude floristique de la forêt marécageuse de Lokoli au Bénin. 101 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 1 records from Contribution to the knowledge of oribatid mites of the genus Austrocarabodes (Acari, Oribatida, Carabodidae) of Madagascar. 12 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 76 records from Données naturalistes de Monsieur François FOURNIER. 17 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 1 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 10 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 3610 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 178 records from Herbarium Universitatis Daugavpiliensis. 4 records from Two new species of the genus Deltomerodes Deuve, 1992 (Coleoptera, Carabidae, Patrobini) from Xizang, China. 57 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 1 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 1797 records from Arthur Chapman Observations. 98 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 3282 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 101 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 349802 records from Hatikka Observation Database. 403 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 71 records from Plecoptera. 45 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 724 records from Données naturalistes de Monsieur JOURDE Rémi. 1 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 40990 records from inatura - Erlebnis Naturschau Dornbirn. 168 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 3 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 4 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 23798 records from Swan Coastal Plain Survey. 3 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 10 records from New Species Of Neoperla Needham And Phanoperla Banks (Plecoptera: Perlidae) From The Philippine Islands. 7 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 32 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 3792 records from Sea water microorganisms Raw sequence reads. 6 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 10 records from ProDelphinus Peru Leatherback Tracking Project (aggregated per 1-degree cell). 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 14 records from NZCS Brownsberg Nature Park Monitoring. 76 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 10362 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 5 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 19 records from Mangelia (Gastropoda, Conoidea) species of the Turkish coasts with description of Mangelia vanaartseni sp. nov.. 2 records from Revision of the spider genus Ischnocolus Ausserer, 1871 (Mygalomorphae: Theraphosidae: Ischnocolinae). 242 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 9 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 13 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 41 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 2 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 17 records from Invasive Non-Native Species, Outer Hebrides. 48 records from AFTT JAX Aerial Survey -Left side- 2014. 17666 records from Naturalis Biodiversity Center (NL) - Crustacea. 94 records from Danish Ants (Formicidae). 38 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 559 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 3 records from A new species, a new combination, and a new record of Crossotarsus Chapuis, 1865 (Coleoptera, Curculionidae, Platypodinae) from China. 12 records from The genus Hoplothrips in Australia (Thysanoptera, Phlaeothripinae), with eleven new species. 4190 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 194151 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 35993 records from Leicestershire and Rutland Environmental Records Centre records 2015-2019. 164896 records from DATAVES. 4088 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 125 records from The Broward College Insect Collection. 111 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 85 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 86 records from Distribution of nanoplankton at trap WR2. 7 records from Taxonomic studies on Dolichothrips (Thysanoptera: Phlaeothripinae), pollinators of Macaranga trees in Southeast Asia (Euphorbiaceae). 459 records from Ecosphère_2017_12_18. 642 records from Flora vascular y no vascular:expedición El Consuelo - Proyecto Boyacá BIO UPTC. 1 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 6 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 6587 records from Fermanagh Flora. 17361 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 1 records from Transfer of two South American ant species from Tapinoma Foerster 1850 to Forelius Emery 1888 (Hymenoptera: Formicidae: Dolichoderinae). 58 records from Isle of Wight non-native invasive species. 3 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 6 records from Description of Bagarius vegrandis, a new species of sisorid catfish from Indochina (Actinopterygii: Siluriformes), with notes on the identity of Bagarius bagarius. 9 records from Weber State University Herbarium. 20 records from Données de la naturaliste Anna Even. 9 records from Happywhale - Peale's Dolphin in South Atlantic Ocean. 28 records from Molecular phylogeny of the genus Lasiopogon (Diptera: Asilidae) and a taxonomic revision of the bivittatus section. 1 records from New species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Brazil and Suriname. 17 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 1 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 84 records from UNCW Aerial Survey 1998-1999. 422 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 3 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 1252 records from Censos de aves en los municipios de Honda (Tolima) y Guaduas (Cundinamarca) - Reexpedicion Chapman. 7923 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 3 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 301 records from SIM-Fungal records compiled by Joan Montón. 4 records from Nueva especie de Aleuropleurocelus Drews y Sampson (Hemiptera: Aleyrodidae) y clave para especies del grupo de forma oval. 70109 records from Western Australian Museum provider for OZCAM. 3 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 478 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 65 records from Colección de mamíferos voladores y no voladores de la Universidad de Nariño. 8 records from Flora vascular y no vascular: expedición Cuenca Media del río Chicamocha - Proyecto Boyacá BIO UPTC. 4 records from Muséum d'Avignon. 184 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 30 records from New Records of ground beetles for Colombia (Coleoptera: Carabidae). 1 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 3 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 1 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 15 records from Inventaire des Octocoralliaires des fonds sédimentaires de la région niçoise. 2614 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 2 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 4 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 54970 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 5 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 2 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 1 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 1 records from Brachymelecta Linsley, 1939, previously the rarest North American bee genus, was described from an aberrant specimen and is the senior synonym for Xeromelecta Linsley, 1939. 1 records from Swiss Occurrence Records of Native Species of Various Faunal Groups. 1 records from Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand. 3 records from The genus Stenoterommata Holmberg, 1881 (Araneae, Pycnothelidae) in the Cerrado and Atlantic Forest from Southeastern and Central Brazil: description of four new species. 679 records from Collection Trichoptera - SMF. 3 records from Happywhale - Arnoux's Beaked Whale in Southern Ocean. 54 records from UWIZM Anoles. 193 records from Pat Livermore's Fungus Records 1976 - 2000. 384075 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 15685 records from NRW Regional Data: South East Wales Non-sensitive species. 3 records from Marine Turtle Conservation Project 2012-2013 (aggregated per 1-degree cell). 6 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 19 records from Taxonomic novelties in Apocynaceae subfam. Asclepiadoideae from New Caledonia. 20514 records from CEPEC herbarium - Centro de Pesquisas do Cacau - Herbário Virtual REFLORA. 14 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 2241 records from Naturalis Biodiversity Center (NL) - Diptera. 95 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 3 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 1 records from A new aquatic beetle family, Meruidae, from Venezuela (Coleoptera: Adephaga). 6 records from Grewia hispidissima Wahlert, Phillipson & Mabb., sp. nov. (Malvaceae, Grewioideae): a new species of restricted range from northwestern Madagascar. 53 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 2 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 51 records from Elaboration de table de tarif de cubage multispécifique (I). 1 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 52 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 16 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 6 records from Insect Collections of Okomu National Park- Nigeria. 38501 records from University of Minnesota Insect Collection. 42277 records from ARABEL - Arachnologia Belgica. 8997 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 1 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 1 records from Capnia Shasta, A New Species In The Californica Group From Northwestern California (Plecoptera, Capniidae). 2984 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2). 48 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 7487 records from Wolli Creek Preservation Society Bird Survey. 63 records from Inventaire des espèces végétales de la vallée de Gounti Yéna (Niamey). 13020 records from MLZ Bird Collection (Arctos). 5 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 2 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 904 records from Gastropod Specimens of the Yamagata Prefectural Museum. 1 records from Northern Cyprus 2010 (aggregated per 1-degree cell). 59 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 2 records from A remarkable new species of Micropeza Meigen (Diptera: Micropezidae) from Caatinga biome, Brazil. 6955 records from Herbarium Senckenbergianum (FR) - Fungi. 189 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 53 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 4 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 1 records from Plant specimens of Bihoro Museum. 2 records from Geometridae de France métropolitaine. 238 records from Vegetación asociada a la ciénaga de Bete, municipio del Medio Atrato, Chocó 2008. 1 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 76 records from Leicestershire and Rutland Aculeate Records. 9 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 4 records from Suivi Temporel des Libellules (STELI). 96 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 71498 records from First Bird Atlas. 3 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 141 records from MMS Marine Mammal Survey, PNW 1989-1990. 8 records from Reptilia ZMK. 1836 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 1 records from Ensemble des données Orthoptères. 3336 records from United Kingdom National Whale Stranding Database 1913-2008. 11 records from The bees of Lebanon (Hymenoptera: Apoidea: Anthophila). 539 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 1 records from Oman 2008: Olive Ridley Turtles of Masirah (aggregated per 1-degree cell). 3 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 1 records from A New Perlodes Species And Its Subspecies From The Balkan Peninsula (Plecoptera: Perlodidae). 126 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 853 records from Inventario de Hymenóptera; parasítica en México. 3 records from New species, synonymy and records of Endomia and Stenidius (Coleoptera: Anthicidae) from Asia. 19665 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 1 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘ Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 25 records from Birds Specimens of Akita Prefectural Museum. 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 20 records from Données naturalistes de LE GLOANEC Vincent. 2145 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-81. 1481 records from MSUM Ichthyology and Herpetology Collections. 792 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 54 records from Epiproct And Dorsal Process Structure In The Allocapnia Forbesi Frison, A. Pygmaea (Burmeister), And A. Rickeri Frison Species Groups (Plecoptera: Capniidae), And Inclusion Of A. Minima (Newport) In A New Species Group. 7122 records from Whale catches in the Southern Ocean. 1 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 1 records from The fossil avifauna of the tar seeps Las Breas de San Felipe, Matanzas, Cuba. 1 records from New insights into polyphyly of the harpacticoid genus Delavalia (Crustacea, Copepoda) through morphological and molecular study of an unprecedented diversity of sympatric species in a small South Korean bay. 1839 records from ERBG AVH data. 11513 records from CABI Africa Invasive and Alien Species data. 516 records from River Biologists' Database (EPA). 1 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 2 records from Seven species of Pseudopecoeloides Yamaguti, 1940 (Digenea, Opecoelidae) from temperate marine fishes of Australia, including five new species. 13267 records from Tiroler Landesmuseum Ferdinandeum. 64 records from Phytoplankton abundance at station Rigel_1_2005-02 in Febraury 2005, Chipana, Chile. 2438 records from Données faune Nature 18 - 2017. 31 records from Odonata records from RSPB Reserves 1970-2009. 384 records from Données supplémentaires Atlas des Mammifères marins. 4 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 163007 records from NBIS Records to December 2016. 25 records from Planktic foraminifera abundance of Hole 51-417B. 1 records from Happywhale - Risso's Dolphin in North Atlantic Ocean. 470 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 583 records from South American Antarctic Marine Biodiversity Literature. 1 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 780 records from California State University, Long Beach Birds. 413 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 12 records from Thirteen new records of ferns from Brazil. 68 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 3 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 46 records from Collection Hydrozoa - ZSM München. 667 records from Happywhale - Leopard seal in Southern Ocean. 29409 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 166 records from NE Scotland other invertebrate records 1800-2010. 6 records from Coleccion Briologica 3T 2020. 2 records from A new species of Tyrannoseira (Collembola: Entomobryidae: Seirini) from the Brazilian coastal region. 2 records from Base de données en ligne d'observations naturalistes de mammifères marins. GEPOG & LPO. 2 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 1084 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 2 records from Review of the millipede family Haplodesmidae Cook, 1895, with descriptions of some new or poorly-known species (Diplopoda, Polydesmida). 7 records from Ameroculodes miltoni, a new species of estuarine amphipod (Crustacea: Malacostraca: Peracarida: Oedicerotidae) from the southeastern United States. 17 records from Census of animals species through Benin from 2011 to 2019. 9 records from The Brazilian Goblin Spiders Of The New Genus Predatoroonops (Araneae: Oonopidae). 1468 records from Données Entomologiques A. HORELLOU 1988-2018. 2 records from A new species of Paralithoxus (Siluriformes: Loricariidae: Ancistrini) from the highlands of Serra da Mocidade, Roraima State, Brazilian Amazon. 21 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 4 records from Rediscovery of Glenurus incalis Banks (Neuroptera: Myrmeleontidae), and notes on the Brazilian species of Glenurus Hagen. 16 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 797 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean. 400 records from Records of Halicarcinus planatus at sub-Antarctic regions. 36 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 105 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 12 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 24 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 3 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 78 records from Données Mammifères marins Aquasearch - Dauphin Passion. 24 records from Huangilene, a new genus for the Miltochrista alikangiae (Strand, 1917) species-group, with descriptions of three new species from Indochina, continental China and Taiwan (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 392 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 723 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 35 records from RECORD Orthoptera Data. 3 records from Sunshine Coast Council Turtle Tracking (aggregated per 1-degree cell). 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 418 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 2 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 256 records from Insect specimen database of Atsugi City Museum. 1524 records from Nematoda of Costa Rica (INBio). 1 records from A Revision of the Nearctic Predaceous Midges in the Bezzia (Bezzia) pulverea complex (Diptera: Ceratopogonidae). 1 records from Revision of the family Acidopsidae Števčić, 2005, and the systematic position of Typhlocarcinodes Alcock, 1900, Caecopilumnus Borradaile, 1902, and Raoulia Ng, 1987, with descriptions of two new genera and five new species (Crustacea: Brachyura: Goneplacoidea). 582 records from MBON POLE TO POLE: ROCKY SHORE BIODIVERSITY OF ARRAIAL DO CABO - BRAZIL. 69 records from Morphologische Daten von Puffinus creatopus. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 1029 records from WTSWW Data: All Taxa (West Wales). 648 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 224 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 1 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 2 records from Happywhale - Southern Bottlenose Whale in Southern Ocean. 44097 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 482 records from Upper Silesian Museum, Bird Observations. 148 records from ISM Ichthyology Collection. 79346 records from South Australian Museum Australia provider for OZCAM. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 7 records from New species and records of Caulleriella (Annelida, Cirratulidae) from shelf and slope depths of the Western North Atlantic Ocean. 7 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 81 records from Données naturalistes de Quentin ROME. 135 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 101 records from SEWBReC Springtails and allies (South East Wales). 3 records from Four new species of Phrynus, Lamarck (Arachnida: Amblypygi) from Mexico. 27 records from Nannofossil abundance of Hole 9-79. 1 records from Polychaeta and Oligochaeta of the Auckland and Campbell Islands, New Zealand, 1941-1945. 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 134 records from The Himalayan Uplands Plant database (HUP Version 1). 1725 records from National Museum of Natural Science. 3 records from A key to the species of Protogamasellus (Acari: Ascidae), with a new species from the Brazilian Pantanal. 27 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 1 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 7 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 14 records from Données de la naturaliste Laurence Beauchamp. 1 records from Collections ichtyologiques et herpétologiques (BOUM). 78 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 105 records from Données naturalistes de Bruno OGER. 2831 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 3 records from First record of the genus Tanaostigma (Hymenopteraı Chalcidoideaı Tanaostigmatidae) from the Afrotropical region with description of three new species. 5 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 4858 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 454 records from Migration and foraging ecology of Greater Shearwater (aggregated per 1-degree cell). 1 records from Données du/de la naturaliste Swoszowski Florie provenant de la base de donnée du SINP Île-de-France CETTIA. 99 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 6 records from NE Scotland fish records 1800-2010. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 339 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 12 records from Happywhale - Humpback Whale in Indian Ocean. 8 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 57919 records from Fichier communal des ongulés. 54 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 5 records from Happywhale - Short-beaked Common Dolphin in North Pacific Ocean. 37616 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 1620 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 2 records from Living Cirripedia. 473 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1572 records from Amundsen Gulf Overwintering Eukaryote Community. 864 records from Tree species composition of natural forest islands in a savanna matrix in the northern Brazilian Amazonia. 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 2 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (PLECHA). 9 records from Données naturalistes de Charlotte PICARD. 1 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 1333 records from University of Nebraska State Museum Birds Collection. 1144 records from University of California Santa Barbara Invertebrate Zoology Collection. 77 records from Fish occurrence in Kama River basin. 2153 records from Entomology Collection at the Natural History Museum of Utah. 407 records from Planktic foraminifera abundance of Hole 45-395. 4 records from Four new Megaselia species (Diptera: Phoridae) from animal carcasses in Bangi, Malaysia. 2983 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 3 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 1 records from Hartland Nature Club Lepidoptera Collection. 26579 records from ALCB - Herbário Alexandre Leal Costa. 2 records from Herbarium specimens of Limoges university (LIMO). 3 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 6 records from Type specimens of Ichneumonidae (Hymenoptera) described by Brèthes held in the Museo Argentino de Ciencias Naturales “ Bernardino Rivadavia ”, Argentina. 17409 records from Fish specimens of Kagoshima University Museum. 3101 records from UTEP Invertebrates (Arctos). 202 records from Diptera Collection of Museum and Institute of Zoology PAS. 55 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 9 records from Fish occurrence in Kuban River basin. 20 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 72 records from Fototrampeo al interior de las áreas del Banco de Hábitat del Meta de Terrasos. 3 records from Revision of Chaetacanthus Seidler, 1922 (Annelida, Phyllodocida, Polynoidae). 8 records from UNCW Norfolk Canyon Aerial Survey - Left side - 2016. 32 records from Flora útil del Municipio de la Huerta, Jalisco. 166 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 647 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 51 records from Taxonomic revision of Ceropegia sect. Huernia (Asclepiadoideae, Apocynaceae) in Saudi Arabia with three new combinations. 8 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 1 records from Happywhale - Green Sea Turtle in North Pacific Ocean. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 132 records from Herbier National de Guinée (HNG). 8 records from New records of Stenopygium Becker (Diptera: Dolichopodidae) from the Neotropical Region, and a key to species. 42 records from Iowa State University Fishes Collection. 1 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 16 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 3 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 232 records from Planktic foraminifera abundance of Hole 21-207. 2497 records from WOLL AVH data. 2 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 327 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 2 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 201 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 17 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 254 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 7 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 24 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 259 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 6189 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 3 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 34 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 978 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 568 records from Planktic foraminifera counts of sediment core V27-178. 314 records from Foraminifera abundance of Hole 64-481. 2 records from Discovery of the genus Micropeneta Pic in China, with description of a new species (Coleoptera: Tenebrionidae: Gnathidiini). 3 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 148 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 72 records from Données des collections d'algues du MNHN. 2506 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 33 records from Coléoptères Silphidés du département du Loiret. 1160 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 2197 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 5 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 31150 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 4 records from Hazel Dormouse in Ireland. 100 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 2 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 2 records from Review of Campsicnemus species from the Atlantic Ocean Islands (Diptera: Dolichopodidae). 199 records from Insects, Outer Hebrides. 15 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 146 records from Philippine Mollusk Symbiont - ICBG Collection. 97 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 194 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 636 records from BioGIS - Vascular plants - Israeli Gene Bank. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1276-1. 106 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 8637 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 12 records from Israel Sea Turtle Tracking Project 2008: Loggerhead & Green Turtles (aggregated per 1-degree cell). 81 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 13 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 5174 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 54 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 31 records from HRC SCC Vessel-Based Monitoring Surveys February 2010. 1 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 30 records from Happywhale - Bryde's whale in South Atlantic Ocean. 4 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 2 records from The first species of the pseudoscorpion genus Lechytia Balzan, 1892 (Pseudoscorpiones, Chthoniidae) from New Zealand. 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 28 records from Registros de dípteros asociados al proyecto: Estratificación espacial del dengue basado en la identificación de factores de riesgo en el departamento del Cauca. 318 records from Marine Turtles. 92 records from Colección de helechos de la FML. 238 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 8 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 6433 records from Données de l'Observatoire de la Faune de Bourgogne. 848 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 694 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 1 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 220 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 89 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 1308 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 100 records from Echinoderms from the Seaflower Biosphere Reserve. 1 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 2 records from A review of the genera Anasillomos Londt, 1983, Oratostylum Ricardo, 1925, and Remotomyia Londt, 1983, with description of a new genus and two new species (Diptera: Asilidae: Stenopogoninae). 1 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 112480 records from Allan Herbarium (CHR). 17 records from Analyses of the recent components of sediment core PS1011-1. 16361 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 14 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 451 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 7 records from Two new sympatric species of Stenocercus (Squamata: Iguania) from the inter- Andean valley of the Mantaro River, Peru. 20 records from Rainforest and cloud forest Scolytodes (Curculionidae, Scolytinae, Hexacolini) from the Arthropods of La Selva inventory in Costa Rica: new species, new synonymy, new records. 5 records from Suivi de la colonie de Pipistrelles de la Petite Ceinture à Paris. 5 records from Discovered online: Hibiscus hareyae sp. nov. of sect. Lilibiscus (Malvaceae), threatened in coastal thicket at Lindi, Tanzania. 96 records from Oceanic Society's Marine Mammal Sightings in Belize 1992 - 2011. 25 records from Revision Of The Australian Coccinellidae (Coleoptera). Genus Novius Mulsant Of Tribe Noviini. 445 records from Enrichment metagenome. 4057 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planctónicas más frecuentes en el Golfo de California. 2664 records from Dragonfly records from the British Dragonfly Society Recording Scheme. 15694 records from eDNA_Subseafloor. 52 records from Colección de macroalgas de la costa Argentina (IADO-UNS-CONICET). 1544 records from Invasive Plant Atlas of the MidSouth (IPAMS). 10 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 1 records from A Catalogue and Historical Study of the Odonata of Ecuador. 3 records from Biodiversity of the Desna river valley and its tributaries. 212 records from Códigos de barras de la vida en peces y zooplancton de México. 565 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 14 records from Description of six new large species of Argentinomyia Lynch-Arribalzaga, 1891 and redescription of Talahua fervida (Fluke, 1945) (Diptera, Syrphidae, Syrphinae). 14 records from Morphological phylogenetic analyses and taxonomic revision of the Panorpa davidi group (Mecoptera: Panorpidae). 427 records from Antarctic Krill occurrence data from Discovery expeditions. 128846 records from KTP Ring Data. 5 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 41 records from Revision of the spider genus Mystaria Simon, 1895 (Araneae: Thomisidae) and the description of a new genus from the Afrotropical region. 85 records from Colección Ornitológica-Museo de Historia Natural Unillanos. 2 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 17 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 730 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 2 records from Two new genera and species of Fidicinini Distant, 1905 with a re-description of Nosola Stål, 1866 (Hemiptera, Auchenorrhyncha, Cicadidae). 1 records from New state and island records of Coccinellidae (Coleoptera) in Hawai‘i, USA. 2 records from Collection botanique Lamy de la Chapelle E. (BOUM). 175 records from Brown University Herbarium. 17 records from Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 166 records from Inventaire de la flore des Pyrénées-Atlantiques 2017 - Littoral. 153 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 1 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 9 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 31282 records from Happywhale - Humpback Whale in North Pacific Ocean. 2 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 10458 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 41 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 54 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases: Cliff-nesting Birds, priority conservation species: Complementary Observations - [2010-2014]. 46 records from Planktic foraminifera abundance of Hole 9-76. 55 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 811 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 2 records from ConDidact Citizen Science Surveys - Amphibians 2007. 2 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 24 records from Dinoflagellate abundance of Hole 28-274. 2 records from Données naturalistes de THÉVENOT Jessica. 1 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 1456 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 225 records from Catalogue and description of the coccolithophores (Haptophyta, Coccolithophyceae), calcareous, scale-bearing microalgae, in New Zealand waters. 63 records from Lucanidae. 1376 records from LISU Herbario Angola. 477 records from nhmc_ob_2019. 697 records from CNAC/Coleccion Nacional de Acaros. 899 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 1 records from Description of two new species of the genus Automate De Man, 1888 (Crustacea: Decapoda: Caridea) from the South China Sea. 19 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 1 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 86 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 34 records from artsprosjektet_51-14_ophiostomatoid_fungi. 112 records from Microzooplankton abundance measured on water bottle samples at station PS65/466-2. 36323 records from Biowide Species data. 91 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Peces). 5 records from Heteragrion lencionii (Odonata: Heteragrionidae) sp. nov. from Serra de Itabaiana National Park, Northeastern Brazil. 6 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 66 records from Reptiles presentes en la colección herpetológica SINCHI de la expedición al Río Apaporis - Proyecto Colombia BIO. 7 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 2 records from Contributions to the study of the grasshopper (Orthoptera: Acrididae Gomphocerinae) courtship songs from Kazakhstan and adjacent territories. 848 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 70 records from The interstitial subsoil fauna of the lower beach level at Sarso Beach, Red Sea (Table 4). 126 records from Données du Geckos vert des Hauts (Phesulma borbonica) du Parc national de La Réunion. 38 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 10 records from Amphibian Specimens of the Yamagata Prefectural Museum. 9 records from New host-plants records of Afrotropical Gelechiidae (Lepidoptera), with description of three new species. 924 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (Abejas). 4 records from Satellite Tracking of Hawksbill Turtle in West Sumbawa, Indonesia (aggregated per 1-degree cell). 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 6 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 2 records from New ants (Hymenoptera: Formicidae) from Micronesia. 1 records from A new anchialine species of Naushonia (Decapoda: Gebiidea: Laomediidae) from the Bahamas. 56 records from Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 76 records from Flora genérica de las gramíneas del estado de Tlaxcala. 153 records from Nannofossil abundance of Hole 84-570. 1878 records from TOPP Summary of SSM-derived Telemetry. 51 records from Leopard and Weddell seal program 1999/2002. 1 records from A new species and southernmost record of Cestrus Townes (Hymenoptera Ichneumonidae, Cryptinae). 697 records from Données naturalistes de Ségolène FAUSTEN. 4 records from Collembola Poduromorpha from two littoral areas of northern Rio de Janeiro Brazil. 116 records from Natural History Museum Maastricht (NL) - Herbarium. 128 records from Foraminifera abundance of sediment core MD81-LC07. 11 records from Mushrooms Flora of Nepal at Central Department of Botany, Tribhuvan University, Nepal. 275 records from MZL Invertebrate Collections. 5 records from Two New Species Of Dictyogenus Klapálek, 1904 (Plecoptera: Perlodidae) From The Jura Mountains Of France And Switzerland, And From The French Vercors And Chartreuse Massifs. 5 records from Crustacean specimens of Bihoro Museum. 1 records from New genus and species of cockroaches from the tribe Brachycolini (Blattaria Blaberidae: Blaberinae) and redescription of the Hormetica strumosa. 2020 records from Invertebrates of the river Tana Basin in Kenya available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section. 361 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 31 records from Collection of Coleoptera. 6 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 2 records from Redescription of Stilobezzia (Stilobezzia) albicoxa Lane & Forattini, 1956 with new synonymy (Diptera: Ceratopogonidae). 13 records from Revision of New World Cosmorrhyncha Meyrick, 1913 (Lepidoptera: Tortricidae: Olethreutinae), with descriptions of five new species. 13 records from Acquario di Genova, Delfini Metropolitani Project, cetacean sightings 2001-2009. 1640 records from Ethnobotanical surveys species in Benin (West Africa). 16 records from Hidden gems in museum cabinets: new species and new distributional records of Scolytodes (Coleoptera: Scolytinae). 3 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 186610 records from Queensland Museum provider for OZCAM. 63 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1379. 10 records from Données naturalistes de Monsieur LAFAGE Denis. 76 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 4 records from Données d'observations d'orthoptères en Auvergne, d'Emmanuel Boitier, de 1998 à 2015.. 1 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 106 records from Actualización de la base de datos de la Colección nacional mexicana de cultivos microbianos. 2 records from Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini. 48 records from NOAA coral reef monitoring invertebrate data from sites across Micronesia from 2009-09-29 to 2015-09-25. 11 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 6365 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 22210 records from NE AVH data. 98 records from Description of lithologic section units of IODP Hole 325-M0033A. 129 records from Biodiversidad selecta de los humedales de Laguna de Términos - Pantanos de Centla (Plantas). 16 records from Earthworm Research Group (UCLan) Earthworm Records (UK). 2020 records from University of Jena, Herbarium Haussknecht - Herbarium JE. 2 records from A new species of Polyamia DeLong (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) representing the first record of the genus from South America. 2436 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 84 records from DUML vessel-based photo-id and biopsy surveys for proposed JAX USWTR site 2012-2015. 719 records from Enquête Lucane. 645 records from CSIC-Real Jardín Botánico-Colección de Algas (MA-Algae). 7 records from Observations de Coléoptères saproxyliques de Frédéric LACOSTE. 13794 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 1570 records from Colección de Alismatales, Apiales, Aquifoliales, Arecales y Asparagales del Museo Botánico CORD - IMBIV. 1 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 1 records from A new species of the genus Diogenes Dana, 1851 (Crustacea: Decapoda: Anomura: Diogenidae) from Gujarat, northwestern India. 903 records from (Table 3) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-657A. 427 records from BioGIS - Reptiles - HUJ collections. 19 records from Microplankton data off Mejillones, 2006, Chile. 13 records from Analyses of the recent components of sediment core PS1222-1. 120127 records from Flora Atlas N.T.. 5216 records from E1 Targeted Locus (Loci). 1183 records from Fishes in the Argentine Sea from 1967 to the present time. 3 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 5 records from Six new species of Anthuridae (Peracarida: Isopoda) from the southern Mexican Pacific. 2 records from Données de la structure SNPN - Société Nationale de Protection de la nature provenant de la base de donnée du SINP Île-de-France CETTIA. 7 records from A new species of Phonotimpus Gertsch & Davis, 1940 (Araneae: Phrurolithidae) from Mexico. 21 records from Données du/de la naturaliste jourdan christian provenant de la base de donnée du SINP Île-de-France CETTIA. 7 records from Revision of the spider genus Hoplopholcus Kulczyński (Araneae, Pholcidae). 899 records from Stable isotopes and content of foraminifera at Hole 130-805C. 18 records from Colección de Referencia de Macroinvertebrados Bentónicos del Museo de Ciencias de la Universidad El Bosque. 6 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 14 records from Mammals collected and illustrated by the Baudin Expedition to Australia and Timor (1800 - 1804): A review of the current taxonomy of specimens in the Muséum national d’Histoire naturelle de Paris and the illustrations in the Muséum d’Histoire naturelle du Havre. 1 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 2 records from Morphological and molecular evidence of a new species of Melanochlamys (Gastropoda: Heterobranchia) from the Bohai Sea, China. 542 records from Butterflies of Ireland. 3 records from Review of the Australian Signal Flies of the Genus Microepicausta (Diptera: Platystomatidae). 16 records from Rare plants database extract from Scottish Natural Heritage. 194 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 12333 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 315 records from Formidabel; Belgian Ants Database. 6 records from New species of Helicopsyche von Siebold 1856 (Trichoptera: Helicopsychidae) from Brazil, including the redescription of Helicopsyche (Feropsyche) planorboides Machado 1957. 36 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 27759 records from CAS Invertebrate Zoology (IZ). 5 records from Ophioderma hendleri sp. nov. (Echinodermata: Ophiuroidea: Ophiodermatidae) and its congeners from the Eastern Pacific. 13 records from Macroinvertebrados bentónicos de playas de arena (Monte Hermoso-Pehuen Có, Buenos Aires, Argentina). 4 records from Leafhopper tribe Coelidiini (Hemiptera: Cicadellidae: Coelidiinae) of the Indian subcontinent. 2352 records from (Table 1) Ranges of Paleocene to middle Eocene planktonic foraminifera in ODP Hole 119-738B. 21 records from Annotated catalog of the type specimens deposited at the fish collection of the “ Universidade Estadual Paulista, Câmpus de São José do Rio Preto ”, São Paulo, Brazil (DZSJRP). 93 records from Taxonomía y distribución de los filópodos (Crustacea: Branchiopoda, Anostraca, Notostraca, Spinicaudata y Laevicaudata) de México. 10356 records from ALCB herbarium - Universidade Federal da Bahia - Herbário Virtual REFLORA. 7018 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Vascular Flora and Habitats: species of conservation concern (RELAPE) - [2010-2014]. 12826 records from Community structure of Archaea in the western North Pacific and the Arctic Ocean. 479 records from Bryophytes specimens of Okinawa Prefectural Museum & Art Museum. 6 records from A new leafhopper genus Discolopeus and nine new species (Hemiptera, Cicadellidae, Deltocephalinae) associated with shrubs, trees and poisonous plants in South Africa. 158 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 7 records from Colección de Aráceas del Jardín Botánico San Jorge. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 15 records from Gabon 2009-10: Pongara, Leatherback Turtles (aggregated per 1-degree cell). 2 records from The species of the bee genus Centris of the “ hyptidis group ” revisited with the description of Centris (Anisoctenodes) new subgenus (Hymenoptera: Apidae: Centridini). 2 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 927 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 3487 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 288 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 3 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 39 records from New species of Culex (Culiciomyia) (Diptera: Culicidae) from Talangaye Forest in Cameroon and descriptions and identification keys for males of the Afrotropical species of the subgenus. 1 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 1 records from SNI California Sea Lions 2014 (aggregated per 1-degree cell). 96 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 3500 records from Pelagic sediment metagenome of Gulf of Kutch. 2832 records from NSW South Coast & ACT plants. 1264 records from EDP Baixo Sabor: Birds - Construction and Reservoir Filling Phases - Vilariça Stream (MC1) [2013-2014]. 1 records from Happywhale - Southern Right Whale Dolphin in South Atlantic Ocean. 3 records from artsprosjektet_48-13_monomyx. 16 records from Crickets of the genus Gryllus in the United States (Orthoptera: Gryllidae: Gryllinae). 1188 records from (Figure 10) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-631A. 1 records from The Odonata of Sulawesi and adjacent islands. Part 8. Revision of the genus Rhinocypha Rambur, 1842 (Chlorocyphidae). 105 records from National Frog Survey of Ireland 2010/2011. 1482 records from Colección Ornitológica de la Universidad del Valle. 91 records from HRC USWEX Aerial-based Shoreline Surveys February and March 2011. 1 records from Chronicle of Nature - Phenology of Insects of State Nature Reserve Kivach. 235 records from USWTR JAX Aerial Survey -Right side- 2009-2010. 19 records from On the Italian species of Drusilla L, 1819, with a note on D. taygetana A (Coleoptera: Staphylinidae, Aleocharinae). 6 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 16 records from Revision of the South American species of Austrothaumalea Tonnoir (Diptera Thaumaleidae). 40 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 20 records from The ‘ red-tailed’ Lasioglossum (Dialictus) (Hymenoptera: Halictidae) of the western Nearctic. 1 records from Données de Mammifères marins. Mission Sanctuaire AGOA de 2012 à 2014. 852 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 29 records from Ten new species of Phyllodoce Lamarck, 1818 (Phyllodocidae, Annelida) from Brazil. 10 records from The Goblin spider genus Xestaspis in Sri Lanka (Araneae: Oonopidae). 38 records from Chronicle of Nature - Phenology of Birds of Central Forest State Nature Biosphere Reserve. 1 records from Contributions to the taxonomy of Minixi Giordani Soika and Alphamenes Van der Vecht (Hymenoptera, Vespidae, Eumeninae), with an identification key to the species of the latter. 1 records from Deep-sea ascidians from Papua New Guinea. 12 records from Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae). 1 records from Indian Hecalina (Hemiptera: Cicadellidae: Deltocephalinae: Hecalini) with description of three new species. 36135 records from NatureServe Network Species Occurrence Data. 5 records from Tagged Seal Location Data from SOGLOBEC. 212 records from Suivi ornithologique par IPA et IKA réalisés dans la Réserve nationale de l’Étang de Saint-Paul en 2012 et 2014. 600 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 1 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 14 records from Cetaceans sighted off the west coast of the South Island, New Zealand, Summer 1970. 153 records from The Gibson spider collection. 467 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 2 records from A new species of Scinax Wagler (Hylidae: Scinaxini) from the tropical forests of Northeastern Brazil. 1 records from A new pelvic-less species of Melanorivulus Costa (Cyprinodontiformes: Cynolebiidae), with a discussion on the pelvic-fin absence in killifishes. 2 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 1 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 3598 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 6 records from Review of Scatimus Erichson (Coleoptera: Scarabaeidae) in Colombia with the description of a new species. 564 records from Wild bees of Belgium. 6 records from Review of the genus Pseudolathra Casey, 1905 (Coleoptera: Staphylinidae: Paederinae) of Réunion Island. 5 records from Données du/de la naturaliste Villalta Rémi provenant de la base de donnée du SINP Île-de-France CETTIA. 28 records from Planktic foraminifera counts of sediment core ELT48.011-PC. 6 records from New species of the plesiomorphic genus Nixonia Masner (Hymenoptera, Platygastroidea, Platygastridae) from South Africa. 756 records from Mokihinui and Karamaea small tributaries and seeps. 4 records from Aspilanta new genus (Heliozelidae) specimen data. 2 records from Orthoptera (Tettigoniidae and Acridoidea) from Miombo woodlands of Central Tanzania with the description of new taxa. 550 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 43 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hemiptera (ZUFMS-HEM). 60 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (rescate). 11 records from Molecular and morphological identification of pistachio armored scale insects (Hemiptera: Diaspididae), with description of a new species. 375 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Plantas Tapachula). 1 records from Diagnostics and updated checklist of Oriental Pseudopostega (Opostegidae) including the matrona species group with a new, extralimital species discovered in the Mediterranean. 7 records from Royal British Columbia Museum Entomology Collection. 4 records from Taxonomic revision of West African cone snails (Gastropoda: Conidae) based upon mitogenomic studies: implications for conservation. 2 records from The first elateroid beetles (Coleoptera: Polyphaga: Elateroidea) from the Upper Jurassic of Australia. 14 records from A review of the Neotropical microcaddisfly genus Acostatrichia Mosely, 1939 with description of a new species from Brazil (Trichoptera: Hydroptilidae: Leucotrichiinae). 12 records from Loggerheads in the Tyrrhenian Sea (aggregated per 1-degree cell). 528 records from Phytoplankton abundance in surface water in January 1996, Chimbote, Peru. 73 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 381 records from Colección Entomológica CDMB. 14 records from NZCS Invertebrates New Collection After 1987. 1 records from Happywhale - Long-finned Pilot Whale in North Pacific Ocean. 2 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 2795 records from Estonian University of Life Sciences Institute of Agricultural and Environmental Sciences Mycological Herbarium. 3 records from Out on a limb: novel morphology and position on appendages of two new genera and three new species of ectoparasitic isopods (Epicaridea: Dajidae) infesting isopod and decapod hosts. 2 records from Revision of the New World species of the genus Dinotrema (Hymenoptera: Braconidae: Alysiinae). 1280 records from Abundance of organic-walled dinoflagellate cysts of sediment core GeoB3603-2. 1 records from Settling the name Diomedea exulans Linnaeus, 1758 for the Wandering Albatross by neotypification. 9225 records from Equatorial Pacific Ocean Targeted loci environmental. 12 records from Données naturalistes de Pauline BALDUCCI. 96443 records from Swiss National Databank of Vascular Plants. 4368 records from DIBA-Parc del Montnegre i el Corredor. 3104 records from University of Tartu Natural History Museum and Botanical Garden Zooloogical Collections. 98 records from Planktic foraminifera abundance of Hole 40-362A. 1 records from A new species of Polietina (Diptera: Muscidae) from South America, with an updated phylogeny of the genus and a review of species’ identity in GenBank. 20 records from Muséum_de_Toulon_et_du_Var_2017_12_18. 358 records from Inventario de macroalgas de Isla Guadalupe, México. 42 records from Cepario de Microorganismos y Hongos Filamentosos de la Universidad del Valle. 527 records from Herbario de la Sociedad Micológica Barakaldo Mikologia Elkartea. 834 records from Fish Collection of National Museum, Philippines. 2 records from A new species of the swimming crab genus, Laleonectes Manning & Chace, 1990 (Crustacea: Brachyura: Portunidae), from the western Indian Ocean. 151 records from Invertebrados del Parque Nacional Arrecife Puerto Morelos. 1 records from Review of East Palaearctic species of Sympycnus Loew, 1857, with a key to species. 654 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 128 records from Colección de insectos de importancia médica del Instituto Nacional de Salud - Ceratopogonidae. 45 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología (Mexicanos). 38 records from Données du naturaliste Bussac Augustin provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from New state records of lady beetles (Coleoptera: Coccinellidae: Coccinellinae) from Missouri and Mississippi, USA. 9 records from New species and new geographical records in Disteniidae (Coleoptera, Chrysomeloidea) with revised keys to species of Novantinoe and American species of Distenia (Distenia). 281 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_93MC. 19143 records from Données naturalistes de Pascal Dupont. 1370 records from Pautas para el manejo y ordenamiento de una pesquería multiespecífica de crustáceos en un área natural protegida: El caso de la Ría Celestún, Yucatán. 1 records from Woodmeadow Invertebrate Survey 2019. 5 records from Inventaire des sangsues - détermination prélèvements de bureau d'études (qualité de l'eau) - Subvention UMS Patrinat. 63 records from Bird specimens of Bihoro Museum. 61 records from Registros de macroinvertebrados acuáticos en un bosque seco del municipio de Honda. 229 records from Monitoreo de la abundancia, riqueza y biodiversidad de aves del Santuario de Flora y Fauna Galeras en 2019. 77 records from HerpMapper. 79 records from Freshwater Fishes of Bulgaria. 162 records from Nannofossil abundance of Hole 4-25. 2 records from A new species of Bicoxidens Attems, 1928 (Diplopoda, Spirostreptida, Spirostreptidae) from northern Zimbabwe. 123 records from Zootaxa. 130 records from NBMB Herps. 2 records from A new species-group of Clubiona Latreille, 1804 and descriptions of four new species from Borneo (Araneae, Clubionidae). 623 records from Registro de vertebrados durante el fototrampeo del convenio 027 - 2014 CVC - Panthera. 551 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 1252 records from Distribution patterns of subtidal macrobenthos in the Tsitsikamma National Park. 2 records from Sigambra sundarbanensis sp. nov. (Annelida, Pilargidae) from the Indian sector of Sundarbans Estuarine System, with remarks on parapodial glands. 414 records from Revues diverses et littérature grise.. 2 records from Porifera Collection - Instituto Nacional de Pesquisas da Amazônia. 3 records from Barsine insolita, a new species from Indochina and India (Lepidoptera, Erebidae, Arctiinae). 1 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 6 records from El género Aleuroparadoxus Quaintance y Baker 1914, con descripción de tres nuevas especies, nuevos registros y clave para las especies (Hemiptera: Aleyrodidae). 660 records from Distribution of major planktic foraminifer at Site 177-1093. 557 records from Expedición Providencia I - INVEMAR. 1 records from Chaetanaphothrips kiyosumianus (Thysanoptera, Thripidae) new to India with first record of the male. 10 records from Planktic foraminifera abundance of Hole 15-154A. 90 records from Damselflies of the genus Argia (Odonata: Coenagrionidae) from Ecuador with descriptions of five new species. 1 records from Données naturalistes d'Arnaud LE NEVÉ. 1 records from A review of New World Malaxa (Hemiptera: Fulgoroidea: Delphacidae). 765 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 13 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 14 records from Happywhale - Leopard seal in South Atlantic Ocean. 17 records from Analyses of the recent components of sediment core PS1219-1. 22956 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 52 records from Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations. 19 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil. 143568 records from Movement patterns of Peruvian Boobies off Isla Lobos de Tierra 2006. 4 records from Données du naturaliste PROVOST romain provenant de la base de donnée du SINP Île-de-France CETTIA. 36 records from Wildlife Sightings in the City of Logan. 4641 records from Birds Specimens. 9 records from Caracterización de Fauna del Banco de Hábitat del Bosque Seco Tropical Antioquia de Terrasos. 2772 records from DMNS Mammal Collection (Arctos). 76 records from Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 4 records from Tortugas Marinas del Golfo de California (aggregated per 1-degree cell). 3 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 35 records from A New Species Of Capnia Pictet, 1841 (Plecoptera: Capniidae) From Kyushu, Japan, With Description Of Male Drumming Signals. 1289 records from A comparison of microbial community composition in four contrasting sediments in the Celtic Sea. 1 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 280 records from Pacific turtle tracks: Turtle-Safe Seas Project. 371 records from Nannofossil abundance of Hole 15-154A. 123 records from New and little-known sun-moth species from Australia (Lepidoptera, Castniidae). 4 records from Taxonomic Accounts With Notes On Spatial Diversity And Relative Abundance Pattern Of Horseflies (Diptera: Tabanidae) From Sonamukhi Protected Forest Area Of West Bengal, India. 34 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 9 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 10075 records from Port Phillip Bay Environmental Study Data 1992-1996 - benthic records. 2 records from A new crab-associated amphipod of the genus Isaeopsis Barnard, 1916 (Amphipoda Senticaudata: Ischyroceridae) from southern Chile. 1945 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 235 records from MCP-Mamiferos - Coleção de Mamíferos. 3 records from Description of Rhamma dawkinsi (Lepidoptera: Lycaenidae) a new mountain butterfly from Colombia. 322 records from Données du Syndicat de la Vallée de l'Orge Aval (SIVOA). 9 records from Revision Of The Spider Genus Neoanagraphis (Araneae, Liocranidae). 2 records from Meniscus Midges (Dixidae) of Ireland. 4 records from Description of a new species of Glassella Campos & Wicksten, 1997 from a coastal lagoon, SE Gulf of California (Crustacea, Decapoda, Pinnotheridae). 1 records from New biogeographical makeup for colonisation of the Baja California Peninsulaı with the description of a new Onthophagus (Coleoptera: Scarabaeidae: Scarabaeinae). 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 702 records from Occurrence database of native plants and animals of south-central Chile. 2896 records from Swiss National Bat Databank: Regional Coordination Western Switzerland (CCO). 1714 records from Données de l'AFB acquises selon le protocole de pêche complète à un ou plusieurs passages. 377 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 2 records from Sierraperla Jewett, 1954 (Plecoptera: Peltoperlidae), Distribution, Egg Morphology And Description Of A New Species. 132 records from Zambian Bat Collections Worldwide. 75 records from PSU-Seagrass Collection. 9 records from A new freshwater shrimp species of the genus Palaemon Weber, 1795 (Decapoda: Caridea: Palaemonidae) from northeastern Japan. 984 records from Vascular plants of south-central China. 15 records from Entomological collection of the National Museum. 106 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 1 records from Miriapodi di alcune grotte della Campania. 1 records from A new species of the greeneye genus Chlorophthalmus (Teleostei: Chlorophthalmidae) from the central North Pacific. 2 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 10 records from Review of the Taiwanese Laccobius Erichson, 1837 (Coleoptera: Hydrophilidae) with description of a new species. 294 records from Helmintos parásitos de peces del sureste de México. 2 records from Cnemaspis rajakarunai sp. nov., a rock dwelling day-gecko (Sauria: Gekkonidae: Cnemaspis) from Salgala, an unprotected lowland rainforest in Sri Lanka. 260 records from Range table from benthic foraminifers in ODP Hole 159-959A. 1 records from A new species of Neobathyclupea from the northern Indian Ocean with comments on N. malayana (Teleostei, Perciformes, Bathyclupeidae). 1 records from Lepidepecreoides stoddartae sp. nov. from the Falkland Islands (Amphipoda: Tryphosidae). 246 records from The Belgica 121 expedition to the Western Antarctic Peninsula: a high resolution biodiversity census. 36 records from Carpoteca de Frutilla del Banco de Germoplasma de Frutilla - Universidad Nacional de Tucumán, Argentina. 6 records from Happywhale - Killer Whale in Arctic Ocean. 11 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 3 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 25 records from Données naturalistes de Hubert GUIMIER. 103 records from Données naturalistes de Hervé BOUYON. 9 records from Données de la collection Rousset -1947-2013. 4 records from Revision of the genus Systellapha Enderlein (Micropezidae, Taeniapterinae). 1 records from A New Free-living Marine Nematode Species of the Genus Graphonema (Nematoda: Chromadorida: Chromadoridae) from Antarctica. 19 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 5 records from Données DREAL Centre-Val de Loire - Faune - 2018. 138 records from Total foraminifera counts of multinet POS247/2_MSN1372. 5 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanteriidae).. 455 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 1 records from Redescriptions of ten chigger mite species (Acariformes: Trombiculidae) from Vietnam. 200 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 2 records from A new species of Enosis Mabille, 1889 (Lepidoptera, Hesperiidae, Hesperiinae) from southern Brazil and notes on Enosis angularis (Möschler, 1877). 2979 records from Highland bird data 2002 - 2003 - non-breeding records. 405 records from RNF - Données du Parc Naturel Régional du Vercors. 86 records from Registros de geckos en Colombia asociado al proyecto: The small world of Lepidoblepharis. 231 records from Insectes Hyménoptères Scollidés de France. 2 records from Description of a new brachypterous scarab species, Orphnus brevialatus (Coleoptera: Scarabaeidae: Orphninae) from East Africa, with notes on flightlessness in the orphnines. 10 records from Revision of the Metallactus generosus species-group with a preliminary evaluation of the effectiveness of the endophallus morphology in distinguishing critical sibling species (Coleoptera: Chrysomelidae: Cryptocephalinae). 990 records from The hoverfly collection (Diptera, Syrphidae) of the International Institute of Tropical Agriculture (IITA) at Calavi (Benin). 4470 records from Weddell Sea macrozoobenthos EASIZ I. 13 records from A new South American species of Banasa Stål (Hemiptera: Heteroptera: Pentatomidae: Pentatominae): from egg to adult. 1 records from Redescription of larva of the South African endemic dobsonfly genus Chloroniella Esben-Petersen, 1924 (Megaloptera, Corydalidae), with a proposed terminology for Corydalidae larval sclerites. 701 records from sea water Picoeukaryotic Community Raw sequence reads Raw sequence reads. 49 records from IOW Natural History & Archaeological Society Marine Records. 1322 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 1484 records from Seawater metagenome Targeted loci environmental. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 30 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 1860 records from Microbial ecology of bacteiral community in sediment from adjacent waters of Rushan Bay. 614 records from Planktic foraminifera assemblage of sediment core ELT49.023-PC. 52 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688E, Part II. 2436 records from Diet results from Adelie penguins at Bechervaise Island and Whitney Point, 2012/13. 1159 records from Heliconiine Butterfly Collection Records from University of Cambridge. 6 records from Hemichordata collection of National Museum of Nature and Science. 97 records from Colección Regional de Equinodermos de la Peninsula de Yucatan. 46 records from Colección de Líquenes Austroamericanos Ex Herbario Regnelliano- FML. 16 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 32 records from Northern elephant seals post-molting 2017 (aggregated per 1-degree cell). 265 records from Fish specimens of Toyama Science Museum. 167 records from Kenai National Wildlife Refuge, Alaska (KNWR) Insect specimens (Arctos). 5 records from Anderemaeus (Acari, Oribatida) - overview, three new species from South America and reassessment of Anderemaeidae supported by ontogeny. 1 records from First record of Cephenniitae in the Bismarck Archipelago, Papua New Guinea, with description of new species of Cephennodes and Cephennomicrus of Mussau and Manus Islands (Coleoptera, Staphylinidae, Scydmaeninae). 1373 records from Colección Limnológica Universidad de Antioquia. 130 records from Rock ptarmigan (Lagopus muta) radio telemetry in Lierne, Norway. 259 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 50 records from Tachinid Recording Scheme - Tachinid fly records verified via iRecord. 3964 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 5 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 1921 records from Conservación y monitoreo de anfibios en riesgo de extinción en Chiapas. 31 records from Données naturalistes de LUPOLI Roland. 15 records from Données du/de la naturaliste JOSSERAND oriane provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 5 records from A new species of Aframomum (Zingiberaceae) from Central Africa. 776 records from Catopsilia butterfly specimens at Museum Zoologi Bogor, Indonesia. 126 records from Inventarios de la biodiversidad en el piedemonte subandino de Yopal. 1 records from Two new species of stargazers of the genus Uranoscopus (Teleostei: Uranoscopidae) from the western Pacific Ocean. 1 records from First record of the myrmicine ant genus Syllophopsis Santschi, 1915 (Hymenoptera Formicidae) from India with description of a new species. 5 records from NC Aquariums Cold Stunned Sea Turtle Monitoring (aggregated per 1-degree cell). 9 records from Données naturalistes de François BRETON. 240 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2004. 1 records from A new species of Platyauchenia Stürm, 1843 (Coleoptera: Chrysomelidae: Cassidinae) from Brazil. 3252 records from Lepidoptera specimen database of Japan. 29 records from Leicestershire and Rutland Reptile Records to 2011. 5640 records from Solenosmilia matrix annotations and VME habitat identification in video from voyage IN2018_V06, Australia (2018). 38 records from Smear slide analysis on sediment core GeoB4214-1. 37 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 142 records from Collection Vermes - ZMB. 1527 records from Culture Collection of Algae. 1 records from Mumetopia interfeles sp. nov., a new species of Anthomyzidae (Diptera) occurring en masse in an urban grassy habitat in Chile: its taxonomy, phylogeny and biology. 9204 records from VIES herbarium - Universidade Federal do Espírito Santo - Herbário Virtual REFLORA. 2730 records from Distribution of planktic foraminifera in surface sediments of the Atlantic Ocean (ATL947). 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-4. 144 records from Diet, Tidal and Vertical Variations of Phytoplankton and Its Environment in Frobisher Bay, Canada, 1980 and 1981. 23 records from New genera for species of Jassa Leach (Crustacea: Amphipoda) and their relationship to a revised Ischyrocerini. 11 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 1 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 79 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 3 records from New species of Condylostylus Bigot (Diptera: Dolichopodidae) from Comoros Madagascar, Tanzania and South Africa, with key to Afrotropical species. 8 records from Données du/de la naturaliste Lantz André provenant de la base de donnée du SINP Île-de-France CETTIA. 378 records from (Table 1) Distribution of planktonic foraminifera from samples spanning the Cretaceous-Tertiary boundary at ODP Hole 207-1259C. 10 records from Read between the lineata: A revision of the tattooed wasps, Zagrammosoma Ashmead (Hymenoptera: Eulophidae), with descriptions of eleven new species. 423 records from Computarización de material complementario en la Colección Regional de Invertebrados del Pacífico mexicano, Instituto de Ciencias del Mar y Limnología, Unidad Académica Mazatlán, UNAM. 14 records from Microzooplankton abundance and biomass at station NBP97-08-29-1. 14082 records from natagora-earlybirds. 1311 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 1 records from Character state variation within Dendrothrips (Thysanoptera: Thripidae) with a revision of the species from China. 1259 records from Hormigas del Museo de Entomología de la Universidad del Valle. 33 records from UWIZM Snakes. 2 records from Type material of land snails (Mollusca: Gastropoda) described from New Zealand by taxonomists in Europe and North America between 1830 and 1934, and the history of research on the New Zealand land snail fauna from 1824 to 1917. 99 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 513 records from Actualización del conocimiento de la diversidad de especies de invertebrados marinos bentónicos de aguas someras (<50m) del Sur del Golfo de México. 1 records from Rediscovered syntypes of Procrangonyx japonicus, with nomenclatural consideration of some crangonyctoidean subterranean amphipods (Crustacea: Amphipoda: Allocrangonyctidae, Niphargidae, Pseudocrangonyctidae). 16 records from Abundance and carbon biomass of phytoplankton at station TT007_9-CTD113. 38 records from Biodiversity survey of Rugezi wetland, Year 2013. 2 records from Artsprosjekt Pyrenomycetes. 4148 records from NOAA coral reef monitoring benthic data from sites across Micronesia from 2009-09-29 to 2015-09-25. 44 records from Microzooplankton abundance and biomass at station TT043_27-1. 61 records from PRESENCIA DE VISÓN AMERICANO EN TIERRA DEL FUEGO, MAGALLANES, CHILE. 21 records from Database of European river lamprey (Lampetra fluviatilis (Linnaeus, 1758)) actual samples deposited in the A.N. Severtsov Institute of Ecology and Evolution. 293 records from Fish and crustacean community in the Western Scheldt (Doel nuclear power station) during winter season 1991-1992. 1 records from Notes on the Dianous aereus complex with description of a new species (Coleoptera, Staphylinidae). 59 records from Northern elephant seals post-breeding 2015 (aggregated per 1-degree cell). 1096 records from Butterflies of Singapore and Peninsular Malaysia (Nymphalidae). 430 records from Archaeal diversity of surface seawater (A3,A5,G3,G5) Targeted Locus (Loci). 268 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 10000 records from FUEL - Herbário da Universidade Estadual de Londrina. 532 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 6 records from Atlantic Forestry Centre Insect Reference Collection. 21 records from Dragonfly (Odonata) species records up to 1997 held by Leicestershire Environmental Resources Centre. 1 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 19 records from Dubai Turtle Rehabilitation Project (aggregated per 1-degree cell). 4 records from A new scale insect host family (Hemiptera: Asterolecaniidae) for Aphytis (Hymenoptera: Aphelinidae) in China. 3 records from Description of a new Patagonian species of Urophonius Pocock (Scorpiones, Bothriuridae), from Meseta de Somuncurá, Argentina. 96 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1381. 115 records from Coleção de Ictiologia ABAM do Campus Sinop da UFMT. 254 records from South Lanarkshire peatland records 2013. 48 records from Content of coarse fraction and G. menardii in sediment corev V25-44. 168 records from (Table 6) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-216. 226 records from Transferts SI Faune - Données naturalistes opportunistes de Cedric DEVILLEGER. 510 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 21 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 2150 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 1 records from Diversity of methyl alkyl succinate synthase genes in hydrocarbon seep sediments (Raw sequence reads). 11 records from New distributional records of Staphylinina in Taiwan, including a new species of Miobdelus Sharp (Coleoptera: Staphylinidae: Staphylininae: Staphylinini). 13 records from Lane 6 Analysis. 206 records from Planktic foraminifera abundance of Hole 15-149. 103 records from Computarización de la colección de myxomycetes y líquenes de Baja California. 2 records from Prioneris butterfly specimens at Museum Zoologi Bogor, Indonesia. 4 records from New records of Chalcidoidea (Hymenoptera) from the Maltese Islands with an updated checklist. 3 records from Taxonomic studies of Japanese Formicidae part 3: genus Vollenhovia.. 153 records from Ibaraki Nature Museum, Fungi collection. 158 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 88 records from Ecological study of the plankton in the port of Ostend in 1965. 40 records from Révision du genre Danuriella Westwood, 1889 (Mantodea). 13754 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 296 records from HRC SCC Aerial-Based Monitoring Survey February 2010. 1 records from Intertidal Euryleptid polyclads and description of a new Stylostomum Lang, 1884 from Maharashtra, India. 20442 records from Trondheim urban biodyversity survey. 91 records from Données du/de la naturaliste LUSTRAT Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Taxonomy and molecular phylogeny of the Platystictidae of Sri Lanka (Insecta: Odonata). 303 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 15 records from New species of Hercostomus Loew, 1857 from Afrotropics (Diptera: Dolichopodidae) and key to Afrotropical fauna. 577 records from Estación Biológica de Doñana - CSIC, Anfibios. 1987 records from R. L. McGregor Herbarium Lichen Collection. 278 records from Abundances of shells of planktic foraminifera species in Upper Miocene sediments from the Indian Ocean and relative abundances of their groups. 434 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 1175 records from UAM Fish Collection (Arctos). 1 records from University of Sargodha Herbarium. 8 records from Bird Specimens of The Cattle Museum. 851 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 71 records from Foraminifera species abundances from tow TT007_7-MOC13. 13 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 122 records from Assemblage of living benthic foraminifera in sediment core GeoB3604-1. 3454 records from UCM Mammal Collection (Arctos). 9280 records from Natural History Museum, Vienna - Herbarium W. 2488 records from University of Colorado, Museum of Natural History Herbarium Bryophyte Collection. 38 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Verdon_2017_12_18. 20 records from Biologia reprodutiva e dieta de Amerotyphlops brongersmianus (Vanzolini, 1976) da Restinga de Jurubatiba, Rio de Janeiro, Brasil (Serpentes: Typhlopidae). 11 records from Mesostigmatic mites (Acari: Mesostigmata) of Saudi Arabia (excluding Phytoseioidea), new records and a key to the known species. 1 records from Description of the larva of Orthemis ferruginea (Fabricius, 1775) (Odonata: Libellulidae). 12 records from Cetacean coordinated transborder monitoring using ferries as platforms of observation off Tunisia 2013-2014 - Atutax. 20 records from Range table from planktonic foraminifers in ODP Hole 178-1096A. 18760 records from Arizona State University Vascular Plant Herbarium. 39 records from Stoneworts in Wales. 89 records from Fungi Collection. 169600 records from Plant niche rather than soil or species shapes the microbiota. 2 records from Ollieopteryx, a new genus of caddisflies from Madagascar (Trichoptera Dipseudopsidae). 136 records from Redland City Council Citizen Science Portal. 470 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 5 records from HBRG Invasive Non-native Plants Dataset. 1 records from New Zealand forest-dwelling skinks of the Oligosoma oliveri (McCann) species-complex (Reptilia: Scincidae): reinstatement of O. pachysomaticum (Robb) and an assessment of historical distribution ranges. 253 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 2184 records from Spatial variation of bacterioplankton in south Atlantic Bight. 1 records from Ampelocalamus stoloniformis, a new combination for Chinese Bambusoideae (Poaceae). 364 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 1149 records from Inventario florístico de la Sierra de Huautla, Morelos. 64 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 875 records from Pollen profile V and Ausfluss at Krumbach, Germany. 1 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 41182 records from University of Michigan Museum of Zoology, Division of Birds. 378 records from (Table 2) Fossil record of foraminifera and ostracoda from Muldsberg clay pit, north Germany. 5 records from Meatopida gen. nov., a new genus to accommodate two species originally described in Atopida White, 1846 (Coleoptera: Scirtoidea: Scirtidae). 59 records from Données naturalistes de AUNEAU Florent. 700 records from uncultured marine picoeukaryote strain:Peuk_V4_NWP2 Raw sequence reads. 4 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 4 records from Taxonomic revision of the Afrotropical scarab beetle genus Cerhomalus Quedenfeldt, 1884 (Coleoptera: Scarabaeidae: Orphninae). 2 records from Redescription of Chrysidea pumiloides Zimmermann, 1956, and description of three new species of Chrysidea from Madagascar (Hymenoptera: Chrysididae). 271 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 5612 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 1 records from Two new species of Neolindus from Peru and Venezuela (Coleoptera: Staphylinidae: Paederinae: Cylindroxystina). 16 records from Suphisellus grossoi sp. n., a new burrowing water beetle from South America and notes on S. flavolineatus (Régimbart, 1889) and S. grammicus (Sharp, 1882) (Coleoptera: Noteridae). 3 records from The endemic Southern African genus Epirinus Dejean, 1833 (Coleoptera: Scarabaeidae: Scarabaeinae) revisited: five new species and two new synonyms. 1 records from A new species of freshwater crab of the genus Phallangothelphusa Pretzmann, 1965, from the foothills of the Serranía Yariguíes of Colombia (Crustacea: Decapoda: Pseudothelphusidae). 51694 records from Fungal Records Database of Britain and Ireland. 2 records from Revision of the genus Psorus Bergroth, 1914 (Hemiptera: Pentatomidae: Discocephalinae). 148 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 9 records from A review of the genus Orionis Shaw (Hymenoptera: Braconidae: Euphorinae) and first records of the genus from South America and the Oriental Region. 130 records from Capercaillie national surveys. 2626 records from La familia Asteraceae en México. Fase VI. 505 records from (Table 3) Protist occurrence in bottom sea ice and surface water samples obtained during a CCGS Amundsen cruise in 2007/2008. 408 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-4. 16 records from Marine gastropod distribution from patagonian shallow waters. 1 records from Two new species of Tenuipalpus Donnadieu, 1875 (Acari: Trombidiformes: Tenuipalpidae) from Iran. 125 records from Mycological collection of the National Museum. 14 records from Salticidae (Arachnida: Araneae) of New Caledonia: Genus Corambis Simon, 1901. 5 records from Distributional data on high altitude endemic taxa of vascular plants from western Balkans. 2 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 4 records from New species of Otiothopinae (Araneae: Palpimanidae) from Colombia. 6677 records from SIO Benthic Invertebrate Collection. 167 records from DASSH Data Archive Centre volunteer survey data. 509 records from Bases ecológicas y sociales para la conservación y el manejo de las abejas sin aguijón en Oaxaca, México. 414 records from Insectos de la expedición en el páramo de Ocetá, Boyacá - Proyecto Boyacá BIO. 106 records from Range table from planktonic foraminifers in ODP Hole 177-1088C. 1536 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 620 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (Coleóptera). 1011 records from UNCW Marine Mammal Aerial Surveys 2006-2007. 3 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 3 records from Description Of Six New Species Of Spiders Of The Genera Lathys (Family: Dictynidae), Marpissa (Family: Salticidae), Misumenoides (Family: Thomisidae), Agroeca (Family: Clubionidae), Gnaphosa (Family: Gnaphosidae) And Flanona (Family: Lycosidae) - From India. 8 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 1312 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 110 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 2 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 1 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 81 records from Modernisation des ZNIEFF du PnrL. 8 records from The West and Central African species of Vepris Comm. ex A. Juss. (Rutaceae) with simple or unifoliolate leaves, including two new combinations. 54 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 196 records from Grand Voyeux - Suivis scientifiques. 4 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 3 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 15 records from Ectopsocidae (Psocodea: ‘ Psocoptera’) from Valle del Cauca and NNP Gorgona, Colombia. 10 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 241 records from irregularia_mexico. 98 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 23 records from Ningaloo Outlook Whale Shark tracking (aggregated per 1-degree cell). 439 records from Antarctic and Subantarctic Asteroid zoogeography. 1104 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 18 records from Coastal and Marine Species Database. 42 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 47 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 102 records from Convention Fédération française de golf - MNHN 2016-2019.. 68570 records from Tasmanian Museum and Art Gallery provider for OZCAM. 100 records from Data from vegetation plots at Atiquipa, Southern Peru. 10 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 1 records from Two deep-sea decapod crustaceans collected off eastern Hokkaido, Japan: Sclerocrangon rex n. sp. (Caridea: Crangonidae) and Munidopsis verrilli Benedict, 1902 (Anomura: Munidopsidae). 417 records from Registros Primates Neotropicales Convocatoria APC. 3 records from New species of Clavigeritae (Coleoptera: Staphylinidae: Pselaphinae) from Malawi and South Africa. 5 records from Swedish Malaise Trap Project (SMTP) - Pimplinae. 312 records from Anammox bacteria in sediment cores of Daya Bay, China. 1 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 6 records from Porifera diversity and distribution data in the Southern Gulf of Mexico. 833 records from HJ herbarium - Universidade Federal de Goiás - Unidade Jataí - Herbário Virtual REFLORA. 3 records from Systematics, Morphology and Biogeography Phylogeny of the Augochlora clade with the description of four new species (Hymenoptera, Apoidea). 154 records from Mollusques dulcicoles de France - Jacques MOUTHON. 729 records from Molluscan specimens from the Astrolabe Reefs (Kadavu, Fiji), 1986-2006. 43 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna” (Reptiles y anfibios). 101 records from BID-Malawi-Geometridae-Biodiversity-Data. 1 records from New Descriptions Of North American Taenionema Larvae (Plecoptera: Taeniopterygidae). 38 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 1 records from Opsarius putaoensis, a new species of subfamily Danioninae (Actinopterygii, Cyprinidae) from the Irrawaddy River basin in northern Myanmar. 11276 records from Collection Aves (bird skins) SMF. 5 records from Revision of Arcastes Baly, 1865 from the Oriental Region (Coleoptera, Chrysomelidae, Galerucinae). 11 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 935 records from SMRU Grey Seal UK 1991-1993. 15 records from New taxa of the tribe Meconematini from South-Pacific and Indo-Malayan Regions (Orthoptera, Tettigoniidae, Meconematinae). 12 records from Taxonomic revision of the genus Probolomyrmex Mayr, 1901 (Hymenoptera: Formicidae: Proceratiinae) for the Neotropical Region. 13 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 169 records from La familia Asclepiadaceae en México. 828 records from Computarización de la Colección de helmintos parásitos de peces del estado de Tabasco. 2 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 5 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 12 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 180 records from Benthic foraminifera abundance of Hole 41-366A. 49 records from Otter survey of Ireland 2004 & 2005. 3678 records from JOI - Herbário Joinvillea. 1 records from A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India. 6 records from A revision of the African wolf spider genus Amblyothele Simon. 1 records from Asya hayvanlari ve zoogeografiyasi hakkinda. Asiatische Beiträge. VIII.. 6 records from Microplankton counts and carbon biomass at station TT007_9-CTD108. 2 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 5 records from A review of Smicronyx Schoenherr (Coleoptera, Curculionidae) of Israel, with description of two new species. 244 records from Planktic foraminifera abundance of Hole 21-207A. 483 records from Happywhale - Gray Whale in North Pacific Ocean. 3 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 2 records from Suivi Temporel des Rhopalocères de France (STERF). 13 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 4 records from Cellaria (Bryozoa, Cheilostomata) from the deep: new species from the southern Zealandian region. 1080 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 68 records from Monitoreo de aves por medio de puntos de conteo en el Santuario de Flora y Fauna Galeras en 2018. 12732 records from NINA Vanndata fisk. 177 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 128 records from Total foraminifera counts of multinet POS247/2_MSN1386. 5 records from Liogenys Guerin-Méneville, 1831 (Coleoptera: Scarabaeidae: Melolonthinae Diplotaxini) of northern South America and Central America: taxonomic overview with four new species. 1 records from New species of the genera Havelockia and Thyone (Echinodermata: Holothuroidea) and first record of T. crassidisca from the southwestern Atlantic Ocean. 240 records from Inventaires des cygnes du département de l'Eure. 4 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 1771 records from CSIRO, fish surveys by the Soela, 1980s. 1 records from First record of a living ditaxiporine catenicellid in the Atlantic, with a description of Vasignyella ovicellata n. sp. (Bryozoa). 1 records from Revision of the African horntail genus Afrotremex (Hymenoptera: Siricidae). 96 records from Peces presentes en la colección ictiológica de la Amazonía Colombiana de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 5234 records from Museu Paraense Emílio Goeldi - Ophidia Collection. 24430 records from EDP Foz Tua: Terrestrial Birds, Winter (point counts) - Ecological Monitoring Program [2011-2017]. 12 records from Post-nesting migration of loggerhead turtles around Japan 2005 (aggregated per 1-degree cell). 46 records from Lepidoptera (Specimens NRM). 47 records from Colección nacional de palmas de Colombia - JBQ. 92 records from ROC RSPB Farmland Species Survey Dataset. 41 records from The cicadas (Hemiptera: Cicadidae) of Ecuador including the description of five new species, a new subtribe, four new synonymies, and fifteen new records. 4 records from Wild boar sightings held by Andy Riches. 10 records from Chronicle of Nature - Phenology of Birds of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 3 records from Bald Head Island 2007: Loggerhead Turtles (aggregated per 1-degree cell). 17 records from First records and two new species of sipunculans (Sipuncula) from the Southern Mexican Pacific. 2245 records from Collection of saproxylic and xylobiont Beetles. 781 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 211671 records from The Danish Environmental Portal, species and habitats-database "Danmarks Miljøportals Naturdatabase". 17 records from Tachinid Recording Scheme - GB and Ireland records. 26 records from A Taxonomic Review of the Trapdoor Spider Genus Myrmekiaphila (Araneae, Mygalomorphae, Cyrtaucheniidae). 3 records from Denitrification bacteria in sediment cores of Daya Bay, China. 2 records from A review of bat research in Thailand with eight new species records for the country. 1016 records from Données de type contact en Guadeloupe. 2122 records from HUCP herbarium - Pontífica Universidade Católica do Paraná PUC - Herbário Virtual Reflora. 325 records from Canadian Museum of Nature Palynology Collection. 6 records from The Sphecid Wasps of the genus Cerceris L, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from the Palearctic Region (part II). (Hymenoptera, Apoidea, Crabronidae). 890 records from Flora superior del Bosque Seco Tropical presente en 10 parcelas ubicadas en el Valle del Cauca. 53 records from IRKU Herbarium: collections of vascular plants. 521 records from Atlas des Poissons et Crustacés d'eau douce de Guadeloupe. 3 records from Inventario multitaxonómico del ANP Médanos de Samalayuca. 649 records from Evaluación del estado actual de las poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en los municipios de Paz de Ariporo y Hato Corozal, Casanare. 9 records from Cybaeus (Araneae: Cybaeidae): the adenes species group of the Californian clade. 2 records from A new species of Cetopsis from the Guiana Shield (Siluriformes: Cetopsidae: Cetopsinae). 130 records from Annales de la Société Linnéenne de Maine-et-Loire. 27 records from Données de Mammifères marins dans les TAAF et autres territoires issues de la bibliographies. Compte cardobs 1007 (Trudelle). 1722 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 11433 records from Insectes Hétéroptères Mirides de France. 3 records from The genus Leucophenga (Diptera, Drosophilidae), part VII: the subpollinosa species group from China, with morphological and molecular evidence. 9 records from Données du naturaliste ROCHAT Didier provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Three new species of Lamprigera Motschulsky (Coleoptera, Lampyridae) from China, with notes on known species. 1 records from Three new species of deep-sea Gromia (Protista, Rhizaria) from the bathyal and abyssal Weddell Sea, Antarctica. 5 records from A new species of Microglanis Eigenmann, 1912 (Siluriformes, Pseudopimelodidae) from rio São Francisco basin, Brazil.. 796 records from Microfossil abundance of Hole 16-158. 450 records from Herbario virtual bosques secos de Colombia - Sección herbario TULV (INCIVA). 467 records from Trawl-survey data from the “expedition Hvar” in the Adriatic Sea (Mediterranean) collected in 1948-1949. 16 records from Données de VINCENT Alexis (SAPROX). 342 records from Nannofossil abundance of Hole 78-543. 8 records from Review of the species of the genus Serrapinnus Malabarba, 1998 (Teleostei: Characidae: Cheirodontinae) from the rio Tocantins-Araguaia basin, with description of three new species. 51 records from Evaluación del riesgo de extinción de setenta y tres especies de lagartijas (Sauria) incluidas en la Norma Oficial Mexicana-059-SEMARNAT-2001. 33635 records from British Antarctic Survey Argos satellite tracking data. 1 records from Happywhale - Sei Whale in North Pacific Ocean. 267 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 95 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 779 records from Empire Wind Digital Aerial Wildlife Surveys for BOEM Lease Area OCS-A 0520, Equinor Wind US LLC, November 2017-October 2018. 39 records from Glasgow Museums BRC: Chrysomelidae. 51 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009 (Región sureste). 6 records from New Species And Records Of Anacroneuria (Plecoptera: Perlidae) From Ecuador And Paraguay. 8 records from An annotated checklist of Belgian Therevidae (Diptera, Asiloidea). 4 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 2 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 752 records from Range table from benthic foraminifers in ODP Hole 172-1054A. 120 records from Growth and age across range extension region of Centrostephanus rodgersii in eastern Tasmania and morphometric comparison of urchins inhabiting kelp versus barrens habitats, Australia (2004-2005). 5 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 2 records from Two new species of the genus Laemostenus Bonelli sg. Antisphodrus Schaufuss from Turkey (Coleoptera: Carabidae: Sphodrini). 1 records from Taxonomic status of Macaronesian Eucyclops agiloides azorensis (Arthropoda: Crustacea: Copepoda) revisited - morphology suggests a Palearctic origin. 7 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 1 records from Happywhale - Clymene Dolphin in South Atlantic Ocean. 511 records from USAC Mammals Collection. 326 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 1 records from Happywhale - Dusky Dolphin in South Pacific Ocean. 5856 records from (Table 2) Mollusc biostratigraphy of facies underlying the 'Braunkohlensande' in the Lauenburg district, north Germany. 83 records from Données du naturaliste Christian Desmier. 263 records from Stone-curlew Annual Surveys. 4 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 2 records from New species of Glossoscolex and Fimoscolex earthworms (Oligochaeta: Glossoscolecidae) from Embrapa Forestry, Paraná, Brazil. 407 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 12 records from Fossil Specimens of Komatsu City Museum. 11 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 84 records from Diversidad y conservación del germoplasma de henequén Agave fourcroydes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 402 records from Données naturalistes de Bernard Lalanne-Cassou. 989 records from Données naturalistes de Franck NOEL. 30 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 137 records from PSUZC-Reptile Collection. 5 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 5 records from Systematic revision of Calligrapha s. str. Chevrolat (Coleoptera: Chrysomelidae, Chrysomelinae). 353 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 5 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 2 records from A new Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from the northern Western Ghats, Maharashtra, India. 259 records from Natura 2000 ZPS Jarny - Mars-la-Tour. 442 records from Avifauna asociada a paisajes rurales degradados en la vereda San Luis, Barrancabermeja - Santander. 855 records from BioGIS - Mammals - SPNI. 5 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 102 records from Chronicle of Nature - Phenology of Birds of Darwin Nature Biosphere Reserve. 5478 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 3 records from Happywhale - Chinstrap Penguin in Southern Ocean. 6 records from Four new species of Scydmaeninae and Pselaphinae (Coleoptera: Staphylinidae) from Yunnan, China. 2 records from South American Coccinellidae (Coleoptera), Part XIX: Overview of Cryptognathini and systematic revision of South American Cryptognatha Mulsant. 1 records from A revision of the Costa Rican species of Stenoeurilla Brailovsky & Barrera (Hemiptera: Heteroptera: Coreidae: Stenoscelideini), with the description of two new species, new distributional records, synonymical note, and key to the known species. 2 records from Revision of Sinonereis Wu & Sun, 1979 (Annelida: Nereididae). 230761 records from SEWBReC Birds (South East Wales). 8 records from The Neotropical species of the genera Pseudespeson L, 1994 and Espeson S, 1882 (Coleoptera: Staphylinidae: Osoriinae). 50 records from Monitoreo de aves por medio de puntos de conteo en el Santuario de Flora y Fauna Galeras en 2016. 51 records from Colección del Herbario de la Universidad de los Llanos. 1 records from Sea Turtles of Nicaragua's Pacific Coast (aggregated per 1-degree cell). 3 records from Notes on slender species of the long-jawed spider genus Tetragnatha (Araneae Tetragnathidae) with description of three new species. 52 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocapra americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 3 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 959 records from Dead benthic foraminifera of surface sediments from the East Atlantic continental margin off Portugal (Table 5 & 7). 4592 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 1 records from Two new Exilisia Toulgoët, 1958 from mainland Africa (Lepidoptera, Erebidae, Arctiinae). 2 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 3 records from A revision of the genus Anadenosternum Athias-Henriot (Acari: Mesostigmata: Parasitidae). 1 records from Valentin Moser Bats. 153 records from annex1. 123 records from Total foraminifera counts of multinet POS247/2_MSN1377. 2 records from Jumping plant-lice (Hemiptera: Psylloidea) of Afghanistan. 28 records from Dinoflagellate abundance of Hole 28-270. 1 records from Review of Allanagrus Noyes & Valentine (Hymenoptera: Mymaridae) with a key to species. 195 records from Assemblage of living benthic foraminifera in sediment core GeoB3706-3. 1 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 1 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 49 records from Phytoplankton abundance at station Rigel_5_2005-02 in Febraury 2005, Chipana, Chile. 18545 records from Extracellular DNA marine sediment Targeted Locus (Loci). 2 records from Microfossil abundance of Hole 21-208. 194 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2008. 37 records from A synopsis of the subgenus Centris (Hemisiella) Moure, 1945 (Hymenoptera: Apidae: Centridini) in Colombia, with description of a new species. 2041 records from marine metagenome Targeted Locus (Loci). 333 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 58 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_Palearctic. 10240 records from Plan de vertebrados de la Patagonia. 61 records from Planktic foraminifera distribution of sediment core TRI171-27. 4 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 226 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 24 records from Swedish Malaise Trap Project (SMTP) - Sepsidae. 1420 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 3 records from New species, genera, families, and range extensions of freshwater bryozoans in Brazil: the tip of the iceberg?. 290 records from AlgaTerra. 1547 records from LTB AVH data. 436 records from Records from the South Australian Seed Conservation Centre. 174 records from Planktic foraminifera abundance of Hole 22-217. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 8482 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 117 records from Distribution of planktonic foraminifera of sediment core SH1972_7. 3 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 7 records from Endophallus structure: a promising tool for cryptic species identification in Timarcha Samouelle, 1819 (Coleoptera: Chrysomelidae: Chrysomelinae). 1 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 734 records from LPO_PACA_2017_12_18. 376 records from HSU Vertebrate Museum Mammals Collection. 33 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 2 records from Targeting a portion of central European spider diversity for permanent preservation. 13 records from Nannofossil abundance of Hole 9-80. 11 records from Centre for Biodiversity Genomics (BIOUG) - Marine Invertebrates. 73 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 1 records from New Prionospio and Laubieriellus (Annelida: Spionidae) species from Southeastern Brazil. 3340 records from Census of species recorded during phytosociological surveys in Benin. 100 records from Nannofossil abundance of Hole 3-15. 262 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 117 records from (Table 2a) Downcore distribution of live benthic foraminifera of sediment core PS1394-1, Weddell Sea. 251 records from 成龍溼地魚類生態紀錄. 303 records from TTRS Mammals. 12 records from Revision of the genus Dinotoperla Tillyard, 1921 (Plecoptera: Gripopterygidae) using morphological characters and molecular data: Establishes two new genera, three new species and updates the larval taxonomy. 2 records from A global revision of the Seahorses Hippocampus Rafinesque 1810 (Actinopterygii: Syngnathiformes): Taxonomy and biogeography with recommendations for further research. 2 records from Lampetra soljani, a new brook lamprey from the southern Adriatic Sea basin (Petromyzontiformes: Petromyzontidae). 820 records from NHMD Amber Collection. 32 records from Marybio Foundation marine mammal shipboard sightings in Bahia San Antonio, Patagonia 2008-2010. 937 records from Bacterial community dynamics during polysaccharide degradation at contrasting sites in the Southern and Atlantic Oceans. 6 records from Données du naturaliste DESCHATRE Thierry provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 1 records from A new large and colourful species of the genus Doto (Nudibranchia: Dotidae) from South Africa. 236075 records from Liste des espèces de la faune sauvage de la base de données naturalistes Faune-France 2018.. 2 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 213 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 46 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 2 records from Bat diversity data by Formosan Golden Bat's Home. 554 records from Point Count Data for TIDE's Private Land (Kern), Belize 2009-2013. 15 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 26 records from Colección Ornitológica del Museo de Historia Natural de la Universidad de la Amazonia. 135 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 1445 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 1 records from Two new and one known marine water mite (Acari: Hydrachnidia: Pontarachnidae) from South-East Africa. 56 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 69 records from Sepsidae (Diptera) records from Britain and Ireland to 1985. 1 records from DUML coastal surveys on the occurrence, distribution and density of marine mammals in Camp Lejeune 2010-2013. 8 records from UTEP Fish (Arctos). 4 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 17 records from The caddisfly genus Protoptila in Costa Rica (Trichoptera: Glossosomatidae). 1 records from A new species of Thamnodynastes Wagler, 1830 from western Amazonia, with notes on morphology for members of the Thamnodynastes pallidus group (Serpentes Dipsadidae, Tachymenini). 12142 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 79 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Pompo) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 1 records from A new species of Anthiadinae (Teleostei: Serranidae) from São Pedro and São Paulo Archipelago, Brazil, Equatorial Atlantic.. 1 records from Rediscovering Anhanga: redescription and considerations on its taxonomic placement (Hemiptera: Heteroptera: Pentatomidae). 30 records from Modelación de la distribución potencial del género Bursera (Burseraceae) en México. 21949 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 315 records from University of Sindh Jamshoro Herbarium. 1 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 4 records from A New Genus of the Spider Family Caponiidae (Araneae, Haplogynae) from the West Indies. 33 records from Densidad poblacional para fauna medida por medio de cámaras trampa en los Valores Objeto de Conservación (VOC) del territorial Andes Occidentales. 18 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) UiT Tromsø Museum. 11 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 2 records from MFS-Plantulas - Herbário Profª. Drª. Marlene Freitas da Silva - Coleção de Plântulas. 516 records from Nannofossil abundance of Hole 15-149. 238 records from List of Macroinvertebrate Species recorded in Vava’u during BioRAP survey. 672 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 2 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 7 records from Rutilans. 19 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 27 records from Monitoreo de mastofauna en corredores biológicos de Chiapas. 3823 records from UTEP Insects (Arctos). 2646 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 2 records from A new genus and two new species in the tribe Selizini (Hemiptera: Fulgoromorpha: Flatidae) with a checklist for the tribe from China. 3860 records from Leicestershire Bryophyte Data. 2 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 2130 records from Collection Pisces SMF. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 4327 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 4 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 1345 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 4363 records from Chandeleur Island 2016 Amplicon Study Raw sequence reads. 20673 records from Microbial biogeography of 925 geothermal springs in New Zealand. 1 records from Happywhale - Black Dolphin in South Atlantic Ocean. 7 records from Banco de Germoplama del Jardín Botánico de Castilla-La Mancha. 23 records from Inventaire Faune. 1167 records from MEXU/Tipos de plantas vasculares. 1 records from New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico. 19 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 85 records from Registros de arañas en el marco del proyecto Influencia de la dieta sobre la toxinología y toxicología en arañas. 1 records from Revision of the genus Carybdea (Cnidaria: Cubozoa: Carybdeidae): clarifying the identity of its type species Carybdea marsupialis. 2 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 3 records from Packer Collection /Madagascar. 4 records from The larva of Amphigomphus somnuki Hämäläinen, 1996 and the first records of the genus Stylogomphus Fraser, 1922 for Thailand (Odonata: Gomphidae). 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt de l'ALLIER (03). 3 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 1224 records from Condition of rocky reef communities around Tasmania: fish surveys, Australia (1992-1995 and 2006-2007). 334 records from University of Valencia cetacean surveys in the Spanish Mediterranean 2000-2003. 6 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-960A. 462 records from Données du/de la naturaliste Dodelin Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 247 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Gill Net. 3658 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 5 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 1180 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 33 records from Insect specimens of Omogo Mountain Museum. 250 records from Observatoire des Mammifères marins de l'Archipel Guadeloupéen. Suivi Dauphins Les Saintes. 3357 records from marine metagenome. 339 records from Données naturalistes de Daniel PAVON. 137 records from Chronicle of Nature - Phenology of Plants of Carpathian Biosphere Reserve. 33 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 1 records from On the taxonomy of the genus Pseudacronicta Kononenko, 2001 (Lepidoptera Noctuidae, Acronictinae): the identity of Acronicta omihsiensis Draeseke, 1928. 355 records from Database on reference specimens for medicinal plants of the Rubiaceae family, conserved at the CNARP herbarium. 8 records from A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae). 183 records from A revision of the minor species group in the millipede genus Nannaria Chamberlin, 1918 (Diplopoda, Polydesmida, Xystodesmidae). 32 records from SFSU - Vascular Plants of the Harry D. Thiers Herbarium at San Francisco State University. 635 records from AICM satellite tracked loggerhead sea turtles from Mozambique 2012 under SWIOFP. 60 records from Colección de Crustáceos del Instituto de Ciencias Naturales (ICN-MHN-Cr). 522 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-127. 2045 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 4055 records from Canadian Museum of Nature Mammal Collection. 16 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 20827 records from Estonian Nature Observations Database. 2 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 5 records from Genome sequencing reveals extraordinary cephalic horns in the Madagascan dung beetle genus Helictopleurus (Coleoptera, Scarabaeinae): insight from a revision of fungicola species group. 1 records from Description of three new velvet geckos (Diplodactylidae: Oedura) from inland eastern Australia, and redescription of Oedura monilis De Vis. 2024 records from Botanical Museum, Copenhagen, Mycology Herbarium. 2 records from A new species of Seira (Collembola: Entomobryidae) from northeastern Brazil. 3496 records from NCSM Mammalogy Collection. 3 records from Description of a new species of Music frogs (Anura, Ranidae, Nidirana) from Mt Dayao, southern China. 554 records from Institut Botanic de Barcelona (IBB, CSIC-Ajuntament de Barcelona), BC-Lichen. 43 records from Hyperbenthos community in the salt marsh of Saeftinghe in 1990 and 1991. 2138 records from Diagnóstico del aprovechamiento de flora y fauna por los mayas del Ejido Petcacab y evaluación de la cacería y pesca, Felipe Carrillo Puerto, Quintana Roo. 3 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 9 records from Integrative taxonomy reveals cryptic diversity in neotropical grasshoppers: taxonomy, phylogenetics, and evolution of the genus Sphenarium Charpentier, 1842 (Orthoptera: Pyrgomorphidae). 10 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 3 records from A new species of the spider genus Phlogiellus (Araneae, Theraphosidae) from Hainan, China. 30 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 4 records from A new South American species of Palaeophileurus Kolbe (Coleoptera: Scarabaeidae: Dynastinae: Phileurini). 306 records from Odonata de Veracruz. 1 records from Revisions to the faunas of Andrena of the Iberian Peninsula and Morocco with the descriptions of four new species (Hymenoptera: Andrenidae). 99 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 9 records from Chinese species of Pediobius Walker (Hymenoptera: Eulophidae). 9 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 93 records from Moluscos Marinhos de Augusto Nobre. 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 282 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 1 records from The Pandemic Blenny, Coralliozetus clausus, a new species of tube blenny endemic to Isla del Coco, Costa Rica (Teleostei: Chaenopsidae). 13 records from Happywhale - Sei Whale in South Pacific Ocean. 100 records from Mushrooms Flora of Nepal at National Herbarium and Plant Laboratories (KATH). 2484 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 24 records from Marine Mammal Observation - Total Denmark 2013-2020. 149 records from The Masao Oita Insect Collection of The University Museum, The University of Tokyo. 722 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 4 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 3814 records from LACM Invertebrate Paleontology. 2 records from NZCS Kabo Studies 1989/1997/2011/2012. 3 records from Boraginaceae (Cynoglossum cherangauiense). 1 records from The genera Agathocles and Surenus (Hemiptera: Heteroptera: Pentatomidae) tribal reassessment, redescription, new synonyms, and description of two new species. 2 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 11 records from Ptilophora variabilis Hartig, 1968, bona species, and description of Ptilophora nebrodensis sp. n. from Sicily (Lepidoptera, Notodontidae). 752 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 1 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 3 records from Medleria gen. nov. adds to the biodiversity of Flatidae (Hemiptera: Fulgoromorpha) in the island of Socotra. 30 records from TRAS LA RUTA DE LAS TORTUGAS GOLFINAS EN LOS CABOS, BCS 2009-2018 !! (aggregated per 1-degree cell). 11 records from CG04_2017_12_18. 1379 records from Composition of the coccolith flora in sediment core GeoB1710-3. 342 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Wolf, (Canis lupus) Wild Boar (Sus scrofa) and Roe Deer (Capreolus capreolus) [camera-trapping] - [2011-2014]. 1 records from New species and new records in American Acanthocinini (Coleoptera, Cerambycidae, Lamiinae). 10 records from The Winter Stoneflies (Plecoptera: Capniidae) Of Mississippi. 7 records from Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 5610 records from Harbour seals GPS telemetry in Baie du Mont Saint-Michel. 3 records from Collection Ephemeroptera - SMF. 1371 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 84 records from The Neotropical cuckoo wasp genus Ipsiura Linsenmaier, 1959 (Hymenoptera: Chrysididae): revision of the species occurring in Brazil. 41 records from Inventario de las mariposas diurnas de las cañadas de Morelos y evaluación de factores que permiten el refugio de fauna con limitantes microclimáticas diferentes al macroclima dominante. 5 records from Inventory of the Heteroptera (Insecta: Hemiptera) in Komaba Campus of the University of Tokyo, a highly urbanized area in Japan. 106 records from FBIP: Identification of polychaetes used as bait. 223 records from Denver Museum of Nature & Science - Entomology. 1 records from Swedish Malaise Trap Project (SMTP) - Strepsiptera. 10 records from New species of Australian microgastrine parasitoid wasps (Hymenoptera: Braconidae: Microgastrinae) documented through the ‘ Bush Blitz’ surveys of national reserves. 171 records from Estado actual de conservación de liebres y conejos en categoría de riesgo en México. 12 records from Review of the plant bug tribe Eccritotarsini (Hemiptera: Heteroptera: Miridae) of India and Sri Lanka with description of two new genera and six new species. 299 records from Relative abundance of planktic foraminifera in sediment core RC08-39. 3772 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 120 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 3 records from Two New Shallow-water Species of Agathotanais (Crustacea: Tanaidacea) from Japan. 131 records from Inventaire et regroupement de données Natura 2000. 2565 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 3007 records from Données de la flore d’Alsace (SBA). 3 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 1 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 541 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 268 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_107MC. 2126593 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 2 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 160 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 59 records from Northern elephant seals post-breeding 2018 (aggregated per 1-degree cell). 4562 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 2 records from The spider wasp genus Telostholus Haupt, 1929 (Hymenoptera, Pompilidae) in Malaysia, with the description of four new species. 454 records from Wikiplantbase #Sicilia. 24 records from NEON Biorepository Zooplankton Collection (Unsorted Bulk Sample). 4 records from Larvae Of The Winter Stonefly Genus Allocapnia (Plecoptera: Capniidae) In Mississippi, Usa. 317 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009 (Región golfo centro). 18 records from Dynamics of coastal eutrophicated ecosystems. (IPMS-PHAEO). 38 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 4 records from TAMUG Kemp's Ridley Nesters 2007-2008 (aggregated per 1-degree cell). 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 1666 records from Distribution of major planktic foraminifer at Site 177-1090. 2023 records from Composición florística y estructura vegetal de una parcela permanente en un relicto de bosque seco tropical en el Caribe colombiano. 299 records from Regroupement de données Oiseaux d'eau. 4 records from Oman 2008: Green Turtles of Masirah (aggregated per 1-degree cell). 25 records from Phenological Center - Birds (Laplandskiy). 108 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 5 records from Four Species of Dulichiidae (Crustacea: Amphipoda) from Japan, with the Description of a New Genus and Two New Species. 8 records from Revision of Pseudexogone Augener, 1922 (Annelida, Polychaeta, Syllidae), and its transfer to Pilargidae. 407 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 331708 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 29 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 5499 records from Bird records for Argyll for the years 2002 and 2003. 307 records from Données naturalistes de Loïc SALAUN. 43 records from nsmk_fish_biodiversity_2019. 11 records from Virginia CZM Wind Energy Area Survey- Left side - January 2014 through March 2016. 200 records from Ibaraki Nature Museum, Fish collection. 8148 records from EDP Foz Tua: Terrestrial Birds (transects) - Ecological Monitoring Program [2009-2012]. 18042 records from Flore Franco-Belge. 9 records from Review of the Inca irroratus species group with description of two new species of Inca LePeletier & Serville, 1828 (Coleoptera, Scarabaeidae, Cetoniinae). 47 records from Fiocruz/CCAMP - Coleção de Campylobacter. 12287 records from EAC - Herbário Prisco Bezerra. 298 records from East Ayrshire Species Database. 3 records from CNIN/Tipos Homoptera. 3998 records from Marine Biological Sample Database, JAMSTEC. 102 records from Otter (Lutra lutra), Outer Hebrides. 11424 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 2 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 2 records from Leif Richardson Vermont Bee Specimens. 1 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 1 records from Validation of the name Pogostemon petelotii (Lamiaceae). 3 records from Nannofossil abundance of Hole 9-79A. 426 records from Données espèces - Expertise IQE 308. 1478 records from Collection Crustacea - ZMB. 287 records from The Living Murray Fish data. 173 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 193 records from Monitoramento da taxocenose de anfíbios no Parque Nacional da Restinga de Jurubatiba. 155 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 23 records from Georgia Aquarium/DomSeTCO Leatherback's of Dominica (aggregated per 1-degree cell). 7 records from Phytoplankton abundance in surface water in 1994, Ancon, Peru. 1 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 6266 records from Long-term Bird Census in Cigu 2004-2017. 10 records from Aerial Survey Baseline Monitoring in the Continental Shelf Region of the VACAPES OPAREA: January 2016 - December 2016 (right side). 2 records from Description of a new genus and four new species of Acaricalini (Acari, Eriophyidae, Phyllocoptinae) from South China. 82 records from CNIN/Tipos Coleoptera. 7 records from Contribution to the AIrotropical Ɨchneumoninae (Hymenoptera, Ɨchneumonidae) Irom Gabon and Sierra Leone, with descriptions oI Iive new species and two new subspecies. 2 records from Range table from planktonic foraminifers in ODP Hole 159-960A. 8858 records from Carabidae records for Britain to 2014. 198 records from Range table from benthic foraminifers in ODP Hole 210-1276A. 2144 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 3 records from Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae). 87 records from Microzooplankton abundance measured on water bottle samples at station PS65/514-2. 495 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 8 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 28 records from Study of epibenthos and demersal fish in and around the thiocarbamate discharge area of the Belgian Continental Shelf (1977-1981). 14 records from New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific. 51 records from (Appendix A1) Calcareous nannofossil counts of ODP Site 207-1258. 1903 records from SANBI: DNA Banking(1987-2011). 15 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 1 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 941 records from The national database for marine data (MADS). 14094 records from Naturalis Biodiversity Center (NL) - Mammalia. 30 records from Nannofossil abundance of Hole 9-82. 34 records from Microzooplankton abundance and biomass at station TT043_11-1. 708 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 1 records from New collections of freshwater crabs from northern Madagascar, with the description of a new species of Foza Reed & Cumberlidge, 2006 (Brachyura, Potamonautidae), and comments on their conservation status. 19 records from Description of lithologic section units of IODP Hole 325-M0035A. 2 records from Four new species of Rhyacophila Pictet 1834 (Trichoptera: Rhyacophilidae) from Southeast Asia. 78 records from Canary Islands - OAG (aggregated per 1-degree cell). 3 records from An annotated type catalogue of the centipedes (Myriapoda: Chilopoda) held in the Zoological Museum Hamburg. 465 records from Ghent university - Zoology Museum - Nematod Collection. 1 records from Swedish Malaise Trap Project (SMTP) - Syrphidae. 1 records from Taxonomic changes in Salyavatinae (Heteroptera: Reduviidae), with an updated generic key. 23 records from Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 547 records from Regroupement de données "papillons menacés" collectées par les réseaux entre 1990 et 2012. 13 records from Calliostomatidae, Colloniidae, Margaritidae, and Solariellidae (Gastropoda: Trochoidea) collected by the Marion Dufresne (MD 55) expedition in southeastern Brazil, with description of a new species of Calliostoma. 2 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 1 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 33 records from Tejidos de los ejemplares colectados en la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 487 records from CSLA - Cal State LA Herbarium. 2125 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 22 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 258 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 1012 records from Database for alien invasive plants occurrences in Germany. 8 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 3558 records from Capture of Primary Biodiversity Data for West African Plants. 4 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 15 records from Gandaca butterfly specimens at Museum Zoologi Bogor, Indonesia. 1233 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 703 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 1 records from Two new species of Bryconamericus Eigenmann (Characiformes: Characidae) from southern Brazil. 43 records from Revision of the genus Dziriblatta Chopard, 1936 (Blattodea, Ectobiidae, Ectobiinae) from North Africa, Spain, and the Macaronesian islands. I. The nine subgenera of the genus. 2412 records from 成龍溼地鳥類生態紀錄. 364 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 1 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 62 records from Benthic foraminifera abundance of Hole 84-566C. 122 records from Strathclyde badger sett surveys 1996-2000. 19 records from UNCW JAX Aerial Survey -Left side- 2017. 158 records from MVZ Hildebrand Collection (Arctos). 679 records from SEFSC Southeast Cetacean Aerial Survey 1992. 2 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 10540 records from Abundance of Rocky Reef Fishes, Invertebrates and Algae, Reef Check California (RCCA), 2006 - 2017. 2462 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 38 records from The ceratioid anglerfishes (Lophiiformes: Ceratioidei) of New Zealand. 5315 records from OUPR - Herbário "Professor José Badini". 103 records from Records of Halieutichthys aculeatus complex (Ogcocephalidae, Lophiiformes). 10 records from Nannofossil abundance of Hole 58-442B. 4 records from Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae). 17 records from Taxonomy and ecology of a new species of Corynura (Hymenoptera: Halictidae: Augochlorini) from Chile and Argentina. 12914 records from National Biodiversity Data Bank. Observation records, 1900-2014. 948 records from Peces de la cuenca alta y media del río Bita, Vichada (Colombia). 100 records from Registros de Palma de cera palma (Ceroxylon quindiuense) por medio de fotografías aéreas en el parque Chingaza. 1 records from A new species of Biffarius Manning & Felder, 1991 (Decapoda: Axiidea Callianassidae) from the intertidal coast of northeastern Brazil. 747 records from Occurrence database of bryophytes and native animals of southern Chile. 1340 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 178 records from Sangmi Lee Research Collection. 55578 records from Larvae of decapods off Portuguese coast from 1986 to 1994. 2 records from Two new species of Corynellus Bates, 1885 (Coleoptera: Cerambycidae: Cerambycinae). 4 records from Données 2015 de l'Observatoire de la Biodiversité des Forêts. 1 records from Taxonomic review of Coccobius species (Hymenoptera: Aphelinidae) from China, with notes on their use in biological control of scale insect pests (Hemiptera: Diaspididae), and description of a new species. 1754 records from California State University, Long Beach Mammals. 6 records from Royal Saskatchewan Museum - Ichthyology Collection. 606 records from Monitoreo de la ocupación del Oso Andino (Tremarctos ornatus) en el Parque Nacional Natural Chingaza. 2639 records from Données mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 2. 4 records from Taxonomy of Peruvian water beetles in the genus Hydrochus Leach, 1817 (Coleoptera: Hydrochidae). 414 records from Percentages of planktonic foraminifera species in sediment core V30-40. 12 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 7 records from A review of the Cyana bianca (Walker, 1856) species-group with descriptions of a new species and a new subspecies from Indochina (Lepidoptera, Erebidae, Arctiinae). 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 41 records from A revision of the Australian species of the genus Melobasis Laporte & Gory 1837 (Coleoptera: Buprestidae), Part 2 (Revision of the nervosa species group). 50 records from Inventaire des Mollusques Sphaeriidae de France. 726 records from données aranéologiques de CORNIC Jean-François. 4 records from Four new and three newly recorded species of Diduga Moore, [1887] (Lepidoptera Erebidae, Arctiinae) from China. 75 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 464 records from Clare Biological Records Centre Dataset 2004-2007. 58 records from Expédition Karubenthos 2012 : données issues des publications. 22 records from Riqueza y distribución de briófitos reófilos en el predio Golconda, ubicado en el municipio de Hato, Santander. 69 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1389. 397 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 254 records from Diatom assamblage in samples from sediment trap OG5. 2 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 3 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 1 records from A new glass sponge genus (Hexactinellida: Euplectellidae) from abyssal depth of the Yap Trench, northwestern Pacific Ocean. 23 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 33 records from Neotropical Acanthoderini (Coleoptera, Cerambycidae, Lamiinae): Synonymies and new status in some genera, new species, transferences and new distributional records. 3066 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 1514 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 13 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 1348 records from Phenology and biological traits of migrating eels sampled by trapping in the survey in the Bresle river (France). 817 records from Registros biológicos asociados al monitoreo de la diversidad de escarabajos en paisajes ganaderos de bosque 2013 - 2017. 1 records from A new freshwater chrysophyte, Chrysomorula cohaerens gen. et sp. nov. (Chrysophyceae, Chrysocapsaceae) from North America. 34 records from Microzooplankton abundance and biomass at station TT043_4-1. 5274 records from Données photographiques validées de la galerie du forum "Le Monde des Insectes". 17147 records from Santa Barbara Museum of Natural History Entomology Collection. 175 records from Occurrence of wild and cultivated yams observed in West Africa and Madagascar from 1996 to 2015. 74 records from Distribution of seabirds at sea in the Gulf of Carpentaria, Australia (1990-1991). 1 records from Further Descriptions Of Western North American Podmosta Larvae And Their Separation From Ostrocerca Larvae (Plecoptera: Nemouridae). 60 records from Revision of the Eurybrachidae XIV. The Australian genera Olonia Stål, 1862 and Stalobrachys gen. nov. (Hemiptera: Fulgoromorpha). 3 records from Revision of the Zethus luzonensis species-group (Hymenoptera: Vespidae: Eumeninae), with description of a new species. 2765 records from Benthos counted on dredged samples during Valdivia cruise VA53. 48 records from Ejemplares de Criptogamas de Chile en el Herbario CORD. 26739 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 15 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 11 records from The species of the genus Diaclina Jacquelin du Val (Coleoptera: Tenebrionidae: Alphitobiini) from Sub-Saharan Africa. 4 records from Happywhale - Short-finned Pilot Whale in North Atlantic Ocean. 15 records from A taxonomic review of the genus Antepipona de Saussure, 1855 (Hymenoptera: Vespidae: Eumeninae) from India. 6 records from EDP Foz Tua Otter (Lutra lutra) [transects] - Ecological Monitoring Program (2011-17). 225 records from Axel W. Erikssons African Bird Collection at Vänersborg Museum. 2 records from A new species of the genus Tetragonopterus Cuvier, 1816 (Ostariophysi: Characiformes: Characidae) from the rio Tocantins drainage, Brazil. 1078 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 12 records from Análisis de los efectos ecológicos del aprovechamiento forestal en el Corredor Biológico Mesoamericano: mamíferos, plantas y sus interacciones. 1449 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 401 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 1 records from Taxonomy of Litoria graminea (Anura: Hylidae), with descriptions of two closely related new species. 57 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 3 records from Banco de Semillas de Boyacá. 46596 records from CAS Botany (BOT). 964 records from Données de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS 2015 Chiroptères, Maculinea, Cistude d'Europe. 5 records from Three New Species Of Aegla (Anomura) Freshwater Crabs From The Upper Uruguay River Hydrographic Basin In Brazil. 3 records from Novel taxa of Cheilostomata Bryozoa discovered in the historical backlogs of the Iziko South African Museum. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 1396 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 18 records from Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 30 records from HRC CRC Small Vessel-Based Monitoring Surveys December 2010. 12 records from List of Lizard species recorded in Vava'u during BioRAP. 4 records from Revision of the Nearctic genus Tritoxa Loew (Diptera: Ulidiidae). 8893 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 10 records from New records and diagnostic notes on large carpenter bees (Hymenoptera: Apidae: genus Xylocopa Latreille), from the Amazon River basin of South America. 85 records from Flux data of NU2_trap (Table A1). 2 records from Revision of the bee genus Chlerogella (Hymenoptera, Halictidae), Part I: Central American species. 1230 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 830 records from Soil DNA extracted from Robinson Ridge, East Antarctica Raw sequence reads. 18 records from Sarcodine counts and carbon biomass at station TT007_7-CTD76. 24 records from Capobula gen. nov., a new Afrotropical dark sac spider genus related to Orthobula Simon, 1897 (Araneae: Trachelidae). 69 records from Relevé de collections de lépidoptères rhopalocères et de coléoptères saproxyliques.. 8 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 1 records from Bishop's University Insect Collection (BUIC). 168 records from Catalogue of the herbarium specimens collected from Discovery Bay and Runaway Bay, Jamaica, West Indies, 1958-1999.. 2139 records from Planktic foraminifera abundance of Hole 15-147. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 3 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 3 records from Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae). 1 records from Lepidoptera of Mordovia State Nature Reserve. 1118 records from Collections data on ecology of bottom animal of the Southern ocean. 977 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 44 records from Review of Afrotropical Glenosema Kieffer (Hymenoptera, Bethylidae) with description of 13 new species. 7 records from DNA barcoding reveals a species group of the genus Campiglossa (Diptera, Tephritidae, Tephritinae) with recognition of a new species from East Asia and previously unknown females of Campiglossa coei (Hardy). 1 records from Renefouqueosis peruviensis, a new genus and species of Stenosini (Coleoptera: Tenebrionidae) from Peru with a key to the Stenosini of the World and notes on the genera Anchomma and Fitzsimonsium. 2 records from Resurrecting the genus Enitharoides Brooks, 1953 (Heteroptera: Nepomorpha: Notonectidae): description of three new species and redescription of Enitharoides brasiliensis (Spinola, 1837), comb. nov.. 5799 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 2925 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 3 records from New species of the Neotropical genus Campatonema Jones (Geometridae, Ennominae) with the first description of the female. 207 records from Chromista Collection of the Seto Marine Biological Laboratory, Kyoto University. 1260 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 1911 records from Fish Collection of Yokosuka City Museum. 195 records from Malawi-Cicindelidae-Biodiversity-Data. 1 records from A taxonomic review of the Korean species of the subgenus Datomicra Mulsant & Rey of the genus Atheta Thomson, with description of a new species (Coleoptera, Staphylinidae, Aleocharinae). 5 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 606 records from MEXU/Flora de Oaxaca. 4075 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 80 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 4434 records from Eulachon migration bottom trawl surveys. 1047 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 17 records from Arizona State University Lois B. O'Brien Collection. 625 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 22 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 376838 records from Pl@ntNet automatically identified occurrences. 4 records from Black Corals (Anthozoa: Antipatharia) from the Southwestern Atlantic. 7793 records from Amphibiens et Reptiles de France (Enquête 2). 18 records from Dolichopodidae of Portugal - dataset 2009-2018. 298 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 43 records from Revision of Japanese species of Nipponomyia Alexander, 1924 (Diptera, Pediciidae). 1352 records from Ravensthorpe Range survey data. 1 records from Scorpaena regina, a new scorpionfish (Teleostei: Scorpaenidae) from the east coast of Queensland, Australia. 31 records from Ictiofauna balseana y helmintos parásitos asociados. 906 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 1 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 68 records from The Italian species of the Chthonius ischnocheles group (Arachnida, Pseudoscorpiones, Chthoniidae), with reference to neighbouring countries. 62 records from Données naturalistes d'Alain BERLY. 7543 records from Herps Specimens. 2272 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 4 records from New species of the leafhopper genera Sophonia and Stenotortor (Hemiptera: Cicadellidae: Evacanthinae) from the Oriental region. 12 records from Analyses of the recent components in the sand fraction of sediment core PS1012-1. 2 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 656 records from Données opportunistes. 31 records from Nanoplankton abundance at station GeoB2012-5. 1 records from Red-throated diver national surveys in Scotland - raw data. 9 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 2287 records from Auburn University Museum of Natural History Mollusks. 2 records from Two new desma-less species of Theonella Gray, 1868 (Demospongiae: Astrophorida: Theonellidae), from the Great Barrier Reef, Australia, and a re-evaluation of one species assigned previously to Dercitus Gray, 1867. 7 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 1336 records from Yoann_BLANCHON_2017_12_18. 16 records from Nannofossil abundance of Hole 52-418. 31 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 21 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 3 records from Les Gymnospermes de l'Herbier du Centre National de Floristique de Côte d'Ivoire. 1576 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 1 records from Peripus, a new genus of Xanthopygina (Coleoptera: Staphylinidae) from South America. 58 records from DMNS Parasite Collection (Arctos). 31 records from Chronicle of Nature - Phenology of Insects of Kaniv Nature Reserve. 2 records from A new brachypterous species of Phoberus MacLeay (Coleoptera: Trogidae) and status changes of species in the East African P. nigrociliatus group. 194 records from Microplankton abundance in the euphotic zone of the Aegean Sea in winter 1995. 19 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 620 records from Estudio taxonómico y zoogeográfico de áreas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, México. 4 records from The cavernicolous Oniscidea (Crustacea: Isopoda) of Portugal. 204 records from Revisión de la subfamilia Asopinae (Hemiptera-Heteroptera-Pentatomidae) para México. 452 records from Nannofossil abundance of Hole 64-476. 18 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 47 records from Données naturalistes de Matthias COLIN. 3991 records from Colección general del plantas vasculares del Herbario JBB. 2 records from Review of the Pulvinaria (Hemiptera: Coccomorpha: Coccidae) species of the Ryukyu Islands, Japan. 26505 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 3 records from Redescription of two species previously regarded as Marphysa de Quatrefagesı 1865 ı with the description of new species of Treadwellphysa Molina-Acevedo and Carrera-Parraı 2017. 4710 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 12 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 41 records from Cowan Tetrapod Collection - Herpetology. 3 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 36794 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 6883 records from SPC NECTALIS Zooplankton/Micronekton specimens, New Caledonia 2014. 111 records from Upper Silesian Museum, Bird Collection. 1 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 16 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 10302 records from Royal Belgian Institute of Natural Sciences Mammal collection. 2268 records from CASES2003_2004. 1 records from Description of a new species of Loxosceles Heineken & Lowe (Araneae, Sicariidae) recluse spiders from Hidalgo, Mexico, under integrative taxonomy: morphological and DNA barcoding data (CO 1 + ITS 2). 61 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Xiloteca). 4592 records from Fife Nature Records Centre combined dataset. 34 records from First records of 31 species of butterflies and moths (Lepidoptera) in Cameroon, with remarks on their elevational ranges. 3 records from The harvestman genus Taracus Simon 1879, and the new genus Oskoron (Opiliones: Ischyropsalidoidea: Taracidae). 3 records from On a new Temnocephala (Platyhelminthes) from Southern Patagonia (Chile, Argentina), with a redescription of T. chilensis and some systematic and biogeographical insights *. 4 records from Notes on the genus Kosmiomiris Kirkaldy (Hemiptera: Miridae: Hyalopeplini) with description of a new species. 9010 records from Elephant Seal Sightings, Macquarie Island. 16 records from A monograph of the genus Maladera Mulsant & Rey, 1871 of China (Coleoptera: Scarabaeidae: Melolonthinae: Sericini). 3 records from New taxa and notes on crickets of the subfamily Landrevinae (Orthoptera: Gryllidae) from Brunei Darussalam, Borneo. 1 records from Muséum de Nîmes. 4592 records from Sediment metagenome. 29 records from Mean density of total metazoan meiofauna and major taxa or groups in the top 10 cm of surface sediment on 25 different dates at DYFAMED station. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 4548 records from BioFokus. 1283 records from Anymals+plants - Citizen Science Data. 208 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 30 records from MFS-Frutos - Herbário Profª. Drª. Marlene Freitas da Silva - Coleção de Frutos. 2 records from Two new species of Nealiolus Mason (Hymenoptera, Braconidae, Brachistinae) reared from pest weevils (Coleoptera, Curculionidae). 16 records from Happywhale - Blue Whale in Southern Ocean. 644 records from Happywhale - Humpback Whale in North Atlantic Ocean. 1 records from A new monotypic genus and new species of lady beetle (Coleoptera: Coccinellidae Coccinellini) from western South America. 7 records from Range table from planktonic foraminifers in ODP Hole 172-1057A. 126 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 2758 records from UMNH Reptiles and Amphibians Collection (Arctos). 8580 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 2 records from Gymnothorax pseudotile sp. nov. (Muraenidae: Muraeninae) from Bay of Bengal India. 349 records from CNAN/Scorpiones. 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 18207 records from The fishes collection (IC) of the
Keywords: GBIF; biodiversity; species occurrences